Polyester composition for metal packaging coatings

CN116438119BActive Publication Date: 2026-10-27EASTMAN CHEM CO
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180072426.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-10-27
Filing Date
2021-10-21
Publication Date
2026-10-27
Estimated Expiration
2041-10-21

AI Technical Summary

Technical Problem

发现基于这种TMCD聚酯的涂料组合物具有改进的耐灭菌性,但通常在耐楔形弯曲性方面存在缺陷

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116438119B_ABST
    Figure CN116438119B_ABST
Patent Text Reader

Abstract

The present invention relates to improved polyester polyol compositions containing 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD). Coating compositions based on this TMCD polyester polyol are able to provide a good balance of desired coating properties such as solvent resistance, acid resistance, dry distillate resistance, microcrack resistance, and flexibility. The TMCD coating compositions are particularly useful for metal packaging applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application generally relates to chemistry. In particular, this application relates to polyester compositions. More specifically, this application relates to polyester compositions containing 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) for coating metals. Background Technology

[0002] Metal containers are commonly used for food and beverage packaging. Containers are typically made of steel or aluminum. Prolonged contact between the metal and the filling product can lead to corrosion of the container. To prevent direct contact between the filling product and the metal, a coating is usually applied to the inside of food and beverage cans. For effectiveness, this coating must possess sufficient properties to protect the packaged product, such as adhesion, corrosion resistance, chemical resistance, flexibility, contamination resistance, and hydrolytic stability. Furthermore, the coating must be able to withstand the processing conditions during can manufacturing and food sterilization. Coatings based on a combination of epoxy and phenolic resins are known to provide a good balance of the required properties and are the most widely used. Some industrial sectors are moving away from food contact polymers prepared with bisphenol A (BPA) (the basic structural unit of epoxy resin). Therefore, there is a need for BPA-free coatings for inner can coatings.

[0003] Polyester resins are of particular interest in the coatings industry as alternatives to epoxy resins due to their comparable properties, such as flexibility and adhesion. 2,2,4,4-Tetramethyl-1,3-cyclobutanediol (TMCD), an alicyclic compound, can be used as a diol component in the preparation of polyesters. Thermoplastics based on TMCD polyesters exhibit improved impact resistance due to the unique structure of TMCD. TMCD also provides improved hydrolytic stability of polyesters due to its secondary hydroxyl functional groups. Both of these properties are highly desirable in thermosetting coatings.

[0004] The use of TMCD polyester-based coatings as an alternative to epoxy resins for inner tank coating applications has attracted considerable interest. Existing work involves coating systems based on slightly crosslinked, high-Tg, medium-molecular-weight TMCD polyesters to withstand the processing conditions during tank manufacturing. However, such systems have been found to have drawbacks in some desired properties, such as corrosion resistance, distillation resistance, and microcrack resistance. Higher crosslinking can lead to improved coating properties, such as corrosion resistance, acid resistance, stain resistance, and distillation resistance. However, such coatings tend to have poor flexibility, which adversely affects microcrack resistance and flexural strength during processing. U.S. Patent Application No. 2018 / 0223126A1 discloses a coating composition for metal packaging based on a TMCD polyester polyol that can be cured using an isocyanate crosslinking agent. The claimed polyester polyol composition is limited to aromatic acids, such as isophthalic acid (IPA) and terephthalic acid (TPA), and does not contain aliphatic acids. Furthermore, in the embodiments of U.S. Patent Application No. 2018 / 0223126A1, most polyesters have a TPA / IPA molar ratio of 30 / 70 or 35 / 65, where TPA is the smaller component. The highest TPA proportion is 40 mol% when a portion of the IPA is replaced by 1,4-cyclohexanedicarboxylic acid. Coating compositions based on this TMCD polyester have been found to have improved sterilization resistance, but generally suffer from deficiencies in wedge bending resistance. Therefore, there remains a need to find a suitable TMCD-containing polyester polyol composition that can provide a good balance of coating properties required for metal packaging applications. Summary of the Invention

[0005] In one embodiment, the present invention provides a coating composition for metal packaging, comprising:

[0006] a. Polyester polyol, which is a reaction product of a monomer, the monomer comprising:

[0007] i. 28 mol% - 60 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol based on the total moles of i-iv.

[0008] ii. Based on the total moles of i-iv, 5 mol%-45 mol% of 2-methyl-1,3-propanediol,

[0009] iii. Based on the total moles of i-iv, 10 mol%-45 mol% of cyclohexanediethanol,

[0010] iv. Based on the total number of moles in i-iv, 1 mol% - 4.5 mol% of trimethylolpropane,

[0011] v. Based on the total moles of v-vii, 45 mol%-100 mol% of terephthalic acid,

[0012] vi. Based on the total number of moles of v-vii, 0 mol%-55 mol% of isophthalic acid, and

[0013] vii. Based on the total molar number of v-vii, the amount of acyclic aliphatic diacids ranging from 0 mol% to 15 mol%, and

[0014] b. At least one crosslinking agent selected from the group consisting of: methyl phenolic resins, isocyanates, and amino resin crosslinking agents.

[0015] The polyester polyol wherein the glass transition temperature (Tg) is 50 to 110°C, the acid value is 0 to 10 mgKOH / g, the hydroxyl value is 10 to 40 mgKOH / g, the number average molecular weight is 5,000 to 20,000 mgKOH / g, and the weight average molecular weight is 10,000 to 100,000; and

[0016] The coating described herein has a solvent resistance of greater than 80 MEK bi-friction as measured by ASTM D7835 and a wedge bending resistance of 70-100% as measured by ASTM D3281 (% qualified).

[0017] In another embodiment, the present invention provides a coating composition for metal packaging, comprising:

[0018] a. Based on the total weight of (a), (b), and (c), 70 wt%–85 wt% of a polyester polyol, which is a reaction product of a monomer comprising:

[0019] i. 28 mol% - 60 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol based on the total moles of i-iv.

[0020] ii. Based on the total moles of i-iv, 5 mol%-45 mol% of 2-methyl-1,3-propanediol,

[0021] iii. Based on the total moles of i-iv, 10 mol%-45 mol% of cyclohexanediethanol,

[0022] iv. Based on the total number of moles in i-iv, 1 mol% - 4.5 mol% of trimethylolpropane,

[0023] v. Based on the total moles of v-vii, 45 mol%-100 mol% of terephthalic acid,

[0024] vi. Based on the total number of moles of v-vii, 0 mol%-55 mol% of isophthalic acid, and

[0025] vii. Based on the total molar number of v-vii, the amount of acyclic aliphatic diacids is 0 mol%-15 mol%.

[0026] b. Based on the total weight of (a), (b), and (c), 12wt%–27wt% of methyl phenolic resin, and

[0027] c. Based on the total weight of (a), (b), and (c), 3 wt%–8 wt% of isophorone diisocyanate,

[0028] The polyester polyol has a glass transition temperature (Tg) of 50 to 110°C, an acid value of 0 to 10 mgKOH / g, a hydroxyl value of 10 to 30 mgKOH / g, a number-average molecular weight of 5,000 to 20,000 mgKOH / g, and a weight-average molecular weight of 10,000 to 100,000; and

[0029] The coating described herein has a solvent resistance of greater than 80 MEK bi-friction as measured by ASTM D7835; and a wedge bending resistance of 70-100% (qualified) as measured by ASTM D3281.

[0030] In another embodiment, the present invention provides a coating composition for metal packaging applications, comprising:

[0031] a. Based on the total weight of (a) and (b), 80 wt%–90 wt% of a polyester polyol, which is a reaction product of a monomer comprising:

[0032] i. 28 mol% - 60 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol based on the total moles of i-iv.

[0033] ii. Based on the total moles of i-iv, 5 mol%-45 mol% of 2-methyl-1,3-propanediol,

[0034] iii. Based on the total moles of i-iv, 10 mol%-45 mol% of cyclohexanediethanol,

[0035] iv. Based on the total number of moles in i-iv, 1 mol% - 4.5 mol% of trimethylolpropane,

[0036] v. Based on the total moles of v-vii, 45 mol%-100 mol% of terephthalic acid,

[0037] vi. Based on the total number of moles of v-vii, 0 mol%-55 mol% of isophthalic acid, and

[0038] vii. Based on the total molar number of v-vii, the amount of acyclic aliphatic diacids ranging from 0 mol% to 15 mol%, and

[0039] b. Based on the total weight of (a) and (b), 10wt%-20wt% of benzoguanamine formaldehyde resin,

[0040] The coating composition further comprises titanium dioxide pigment, and the polyester polyol has a glass transition temperature (Tg) of 50 to 110°C, an acid value of 0 to 10 mg KOH / g, a hydroxyl value of 10 to 30 mg KOH / g, a number-average molecular weight of 5,000 to 20,000 mg KOH / g, and a weight-average molecular weight of 10,000 to 100,000; and the coating has a solvent resistance of greater than 80 MEK bi-friction as measured by ASTM D7835 and a wedge bending resistance of 65-100% as measured by ASTM D3281 (% qualified).

[0041] In another embodiment, the present invention provides a coating composition for metal packaging, comprising:

[0042] a. Based on the total weight of (a), (b), and (c), 70 wt%–85 wt% of a polyester polyol, which is a reaction product of a monomer comprising:

[0043] i. 28 mol% - 60 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol based on the total moles of i-iv.

[0044] ii. Based on the total moles of i-iv, 5 mol%-45 mol% of 2-methyl-1,3-propanediol,

[0045] iii. Based on the total moles of i-iv, 10 mol%-45 mol% of cyclohexanediethanol,

[0046] iv. Based on the total number of moles in i-iv, 1 mol% - 4.5 mol% of trimethylolpropane,

[0047] v. Based on the total moles of v-vii, 45 mol%-100 mol% of terephthalic acid,

[0048] vi. Based on the total number of moles of v-vii, 0 mol%-55 mol% of isophthalic acid, and

[0049] vii. Based on the total molar number of v-vii, the amount of acyclic aliphatic diacids is 0 mol%-15 mol%.

[0050] b. Based on the total weight of (a), (b), and (c), 10wt%–20wt% of benzoguanamine formaldehyde resin, and

[0051] c. Based on the total weight of (a), (b), and (c), 5 wt%–12 wt% of isophorone diisocyanate,

[0052] The coating composition further comprises titanium dioxide pigment; and

[0053] The polyester polyol has a glass transition temperature (Tg) of 50 to 110°C, an acid value of 0 to 10 mgKOH / g, a hydroxyl value of 10 to 30 mgKOH / g, a number-average molecular weight of 5,000 to 20,000 mgKOH / g, and a weight-average molecular weight of 10,000 to 100,000; and

[0054] The coating described herein has a solvent resistance of greater than 80 MEK bi-friction as measured by ASTM D7835 and a wedge bending resistance of 75-100% (qualified) as measured by ASTM D3281.

[0055] In another embodiment, the present invention provides a white coating for metal packaging applications, comprising:

[0056] a. Based on the total weight of (a) and (b), 80 wt%–90 wt% of a polyester polyol, which is a reaction product of a monomer comprising:

[0057] i. Based on the total moles of i-iv, 28 mol%-60 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD),

[0058] ii. Based on the total moles of i-iv, 5 mol%-45 mol% of 2-methyl-1,3-propanediol (MP diol),

[0059] iii. Neopentyl glycol (NPG) in amounts ranging from 10 mol% to 45 mol% based on the total moles of i-iv.

[0060] iv. Based on the total moles of i-iv, 1 mol%-4.5 mol% of trimethylolpropane (TMP),

[0061] v. Based on the total number of moles of v-vii, 80 mol%-100 mol% of terephthalic acid (TPA),

[0062] vi. Based on the total number of moles of v-vii, the amount of isophthalic acid (IPA) from 0 mol% to 20 mol%, and

[0063] vii. Based on the total molar number of v-vii, the amount of acyclic aliphatic diacids ranging from 0 mol% to 15 mol%, and

[0064] b. Based on the total weight of (a) and (b), 10wt%-20wt% of benzoguanamine formaldehyde resin,

[0065] The coating composition further comprises titanium dioxide pigment, and the polyester polyol has a glass transition temperature (Tg) of 50 to 110°C, an acid value of 0 to 10 mg KOH / g, a hydroxyl value of 10 to 30 mg KOH / g, a number-average molecular weight of 5,000 to 20,000 mg KOH / g, and a weight-average molecular weight of 10,000 to 100,000; and the coating has a solvent resistance of greater than 80 MEK bi-friction as measured by ASTM D7835 and a wedge bending resistance of 65-100% as measured by ASTM D3281 (% qualified).

[0066] In yet another embodiment, the present invention provides a white coating with improved coating properties for metal packaging applications, comprising:

[0067] a. Based on the total weight of (a), (b), and (c), 70 wt%–85 wt% of a polyester polyol, which is a reaction product of a monomer comprising:

[0068] i. Based on the total moles of i-iv, 28 mol%-60 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD),

[0069] ii. Based on the total moles of i-iv, 5 mol%-45 mol% of 2-methyl-1,3-propanediol (MP diol),

[0070] iii. Neopentyl glycol (NPG) in amounts ranging from 10 mol% to 45 mol% based on the total moles of i-iv.

[0071] iv. Based on the total moles of i-iv, 1 mol%-4.5 mol% of trimethylolpropane (TMP),

[0072] v. Based on the total number of moles of v-vii, 80 mol%-100 mol% of terephthalic acid (TPA),

[0073] vi. Based on the total number of moles of v-vii, the amount of isophthalic acid (IPA) from 0 mol% to 20 mol%, and

[0074] vii. Based on the total molar number of v-vii, the amount of acyclic aliphatic diacids is 0 mol%-15 mol%.

[0075] b. Based on the total weight of (a), (b), and (c), 10wt%–20wt% of benzoguanamine formaldehyde resin, and

[0076] c. Based on the total weight of (a), (b), and (c), 5 wt%–12 wt% of isophorone diisocyanate (IPDI),

[0077] The coating composition further comprises titanium dioxide pigment. The polyester polyol has a glass transition temperature (Tg) of 50 to 110°C, an acid value of 0 to 10 mg KOH / g, a hydroxyl value of 10 to 30 mg KOH / g, a number-average molecular weight of 5,000 to 20,000 mg KOH / g, and a weight-average molecular weight of 10,000 to 100,000. The coating also exhibits solvent resistance greater than 80 MEK bi-friction as measured by ASTM D7835 and wedge bending resistance (% qualified) of 75-100 as measured by ASTM D3281.

[0078] In yet another embodiment, the present invention provides a coating with improved coating properties for metal packaging applications, comprising:

[0079] a. Based on the total weight of (a), (b), and (c), 70 wt%–80 wt% of a polyester polyol, which is the reaction product of a monomer comprising:

[0080] i. Based on the total moles of i-iv, 28 mol%-60 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD),

[0081] ii. 5 mol% to 45 mol% of 2-methyl-1,3-propanediol (MP diol) based on the total moles of i-iv.

[0082] iii. Neopentyl glycol (NPG) in amounts ranging from 10 mol% to 45 mol% based on the total moles of i-iv.

[0083] iv. Based on the total moles of i-iv, 1 mol%-4.5 mol% of trimethylolpropane (TMP),

[0084] v. Based on the total number of moles of v-vii, 80 mol%-100 mol% of terephthalic acid (TPA),

[0085] vi. Based on the total number of moles of v-vii, the amount of isophthalic acid (IPA) from 0 mol% to 20 mol%, and

[0086] vii. Based on the total molar number of v-vii, the amount of acyclic aliphatic diacids is 0 mol%-15 mol%.

[0087] b. Based on the total weight of (a), (b), and (c), 12wt%–27wt% of methyl phenolic resin, and

[0088] c. Based on the total weight of (a), (b), and (c), 3 wt%–8 wt% of isophorone diisocyanate (IPDI),

[0089] The polyester polyol wherein the glass transition temperature (Tg) is 50 to 110°C, the acid value is 0 to 10 mgKOH / g, the hydroxyl value is 10 to 30 mgKOH / g, the number average molecular weight is 5,000 to 20,000 mgKOH / g, and the weight average molecular weight is 10,000 to 100,000; and the coating wherein the coating has a solvent resistance greater than 80 MEK bi-friction as measured by ASTM D7835 and a wedge bending resistance of 70-100% (qualified) as measured by ASTM D3281. Attached Figure Description

[0090] Figure 1 An improved metal bead roller is shown forming beads on a metal plate. Detailed Implementation

[0091] definition:

[0092] Throughout this specification and the following claims, numerous terms will be used, which will be defined to have the following meanings.

[0093] "Alcohol" refers to a chemical containing one or more hydroxyl groups.

[0094] "Aldehyde" refers to a chemical containing one or more -C(O)H groups.

[0095] "Acyclic" refers to compounds or molecules that do not have atomic rings in their structure.

[0096] "Aliphatic" refers to compounds with non-aromatic structures.

[0097] "Dicarboxylic acid" refers to a compound that has two carboxyl functional groups.

[0098] Numerical values ​​can be expressed as “about” or “approximately” to a given number. Similarly, a range can be expressed herein as “about” to a particular value and / or “about” to another particular value. When such a range is expressed, the other side includes from one particular value and / or to another particular value. Similarly, when a numerical value is expressed as an approximation using the antecedent “about”, it should be understood that a particular value forms the other side.

[0099] As used herein, the terms “a / an” and “the / described” mean one or more species.

[0100] As used herein, the term “and / or” when used in a list of two or more items means that any one of the listed items may be used alone, or any combination of two or more of the listed items may be used. For example, if a composition is described as containing components A, B and / or C, the composition may contain: A alone; B alone; C alone; a combination of A and B; a combination of A and C; a combination of B and C; or a combination of A, B and C.

[0101] As used herein, the term “comprising / comprises / comprise” is an open transitional term used to transition from an object described before the term to one or more elements described after the term, wherein one or more elements listed after the transitional term are not necessarily the only elements constituting the object.

[0102] As used in this article, the term “having / has / have” has the same open-ended meaning as “includes” provided above.

[0103] As used in this article, the term "including (including / includes / include)" has the same open-ended meaning as "include" provided above.

[0104] As used in this article, “selected from” can be used with “or” or “and”. For example, “Y selected from A, B and C” means that Y can be A, B or C alone. Or, “Y selected from A, B or C” means that Y can be: A, B or C alone; or, a combination of A and B, a combination of A and C, a combination of B and C, or a combination of A, B and C.

[0105] As used herein, a numerical range is intended to include the starting value and the ending value within that range, as well as all values ​​and ranges between the starting and ending values. For example, a range of 40°C to 60°C includes a range of 40°C to 59°C, a range of 41°C to 60°C, a range of 41.5°C to 55.75°C, and ranges of 40°C, 41°C, 42°C, 43°C, etc., up to 60°C.

[0106] The inventors have unexpectedly discovered that coating compositions based on certain TMCD polyester polyol compositions can provide the desired coating properties for metal packaging applications, such as a good balance of solvent resistance, acid resistance, distillation resistance, microcrack resistance, and flexural strength.

[0107] In one embodiment of the present invention, a coating composition with improved coating properties for metal packaging applications is provided, comprising:

[0108] a. Polyester polyol, which is a reaction product of a monomer, the monomer comprising:

[0109] i. Based on the total moles of i-iv, 28 mol%-60 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD),

[0110] ii. Based on the total moles of i-iv, 5 mol%-45 mol% of 2-methyl-1,3-propanediol (MP diol),

[0111] iii. Based on the total moles of i-iv, 10 mol%-45 mol% of cyclohexanediethanol (CHDM),

[0112] iv. Based on the total moles of i-iv, 1 mol%-4.5 mol% of trimethylolpropane (TMP),

[0113] v. Based on the total moles of v-vii, 45 mol%-100 mol% of terephthalic acid (TPA),

[0114] vi. Based on the total number of moles of v-vii, the amount of isophthalic acid (IPA) from 0 mol% to 55 mol%, and

[0115] vii. Based on the total molar number of v-vii, the amount of acyclic aliphatic diacids ranging from 0 mol% to 15 mol%, and

[0116] b. One or more crosslinking agents selected from the group consisting of: methyl phenolic resins, isocyanates, and amino resin crosslinking agents.

[0117] The polyester polyol wherein the glass transition temperature (Tg) is 50 to 110°C, the acid value is 0 to 10 mgKOH / g, the hydroxyl value is 10 to 40 mgKOH / g, the number average molecular weight is 5,000 to 20,000 mgKOH / g, and the weight average molecular weight is 10,000 to 100,000; and the coating wherein the coating has a solvent resistance greater than 50 MEK bi-friction as measured by ASTM D7835 and a wedge bending resistance of 70-100% (qualified) as measured by ASTM D3281.

[0118] In another embodiment, the coating has a microcrack resistance rating of 2-5, a total distillation resistance rating of 70-100 (%), and a 5% acetic acid vapor resistance rating of 40-100 (%), as measured by the method specified in the Examples section.

[0119] In some embodiments of the invention, the amount of TMCD(i) is 28 mol%-60 mol%, 35 mol%-58 mol%, or 45 mol%-55 mol% based on the total number of moles of (i)-(iv).

[0120] In some embodiments of the invention, the amount of MP diol (ii) is 5 mol%-50 mol%, 6 mol%-30 mol%, 8 mol%-15 mol%, 10 mol%-45 mol%, 15 mol%-40 mol%, 20 mol%-35 mol%, or 25 mol%-50 mol% based on the total number of moles of (i)-(iv).

[0121] In some embodiments of the present invention, the amount of CHDM(iii) is 10 mol%-45 mol%, 20 mol%-43 mol%, 30 mol%-40 mol%, or 10 mol%-40 mol%; based on the total number of moles of (i)-(iv).

[0122] In some embodiments of the present invention, the amount of TMP(iv) is 1 mol%-4.5 mol%, 1.5 mol%-4.2 mol%, 2 mol%-4 mol%, or 1 mol%-4 mol%; based on the total number of moles of (v)-(vii).

[0123] In some embodiments of the present invention, the amount of TPA(v) is 45mol%-100mol%, 47mol%-90mol%, 50mol%-80mol%, or 60mol%-100mol%; based on the total number of moles of (v)-(vii).

[0124] In some embodiments of the present invention, the amount of IPA(vi) is 0 mol%-55 mol%, 8 mol%-51 mol%, 16 mol%-46 mol%, or 0 mol%-40 mol%; based on the total number of moles of (v)-(vii).

[0125] In some embodiments of the present invention, the amount of the acyclic aliphatic diacid (vii) is 0 mol%-15 mol%, 2 mol%-10 mol%, or 4 mol%-8 mol%; based on the total number of moles of (v)-(vii).

[0126] In another embodiment, based on the total number of moles of (i)-(iv), the amount of TMCD(i) is 45 mol%-55 mol%, based on the total number of moles of (i)-(iv), the amount of MP diol(ii) is 8 mol%-15 mol%, based on the total number of moles of (i)-(iv), the amount of CHDM(iii) is 30 mol%-40 mol%, based on the total number of moles of (i)-(iv), the amount of TMP(iv) is 2 mol%-4 mol%, based on the total number of moles of (v)-(vii), the amount of TPA(v) is 50 mol%-80 mol%, based on the total number of moles of (v)-(vii), the amount of IPA(vi) is 6 mol%-46 mol%, and the amount of acyclic aliphatic diacid(vii) is 4 mol%-8 mol%.

[0127] In another embodiment, the total molar amount of TMCD(i) based on (i)-(iv) is 28 mol%-60 mol%, the total molar amount of MP diol(ii) based on (i)-(iv) is 25 mol%-50 mol%, the total molar amount of CHDM(iii) based on (i)-(iv) is 10 mol%-40 mol%, the total molar amount of TMP(iv) based on (i)-(iv) is 1 mol%-4 mol%, the total molar amount of TPA(v) based on (v)-(vii) is 60 mol%-100 mol%, the total molar amount of IPA(vi) based on (v)-(vii) is 0 mol%-40 mol%, and the total molar amount of acyclic aliphatic diacid(vii) is 0 mol%-15 mol%.

[0128] The cyclohexanediethanol comprises 1,4-cyclohexanediethanol (1,4-CHDM), 1,3-cyclohexanediethanol (1,3-CHDM), 1,2-cyclohexanediethanol (1,2-CHDM), and mixtures thereof. Ideally, the cyclohexanediethanol is 1,4-CHDM, 1,3-CHDM, or a mixture thereof. In one embodiment, the cyclohexanediethanol is 1,4-CHDM.

[0129] The TPA includes terephthalic acid and its esters, such as dimethyl terephthalate.

[0130] The IPA includes isophthalic acid and its esters, such as dimethyl isophthalate.

[0131] The acyclic aliphatic diacid includes C4-C 12 Diosmin and its esters, such as succinic acid, adipic acid, sebacic acid, dodecanoic acid and its methyl esters; and (hydrogenated) dimer acids (C 36Ideally, when using long-chain diacids (>C), 10 When these are present, their proportions are relatively small, for example, 1 mol%-5 mol%, 1 mol%-4 mol%, 1 mol%-3 mol%, or 1 mol%-2 mol%. In one embodiment, the acyclic aliphatic diacid is adipic acid in a proportion of 4 mol%-8 mol%.

[0132] The glass transition temperature (Tg) of the polyester polyol is 50 to 110°C, 55 to 105°C, 60 to 100°C, 65 to 100°C, 70 to 100°C, 75 to 100°C, 80 to 100°C, 70 to 95°C, 75 to 95°C, 80 to 95°C, 70 to 90°C, 75 to 90°C, or 80 to 90°C.

[0133] The number-average molecular weight of the polyester polyol is 5,000-20,000, 7,000-20,000, or 10,000-20,000 g / mol; the weight-average molecular weight is 10,000-100,000, 20,000-100,000, 30,000-100,000, or 30,000-80,000 g / mol.

[0134] The acid value of the polyester polyol is 0-10, 0-8, 0-5, 0-3, 0-2, 0-1, 1-5, 1-4, 1-3, 2-5 or 3-5 mgKOH / g.

[0135] The hydroxyl value of the polyester polyol is 10-40, 11-35, 12-30, 13-25 or 14-20, 10-30 or 10-20 mgKOH / g.

[0136] The specific logarithmic viscosity of the polyester polyol is 0.05-0.8, 0.1-0.7, 0.2-0.7, 0.3-0.7, 0.4-0.7, 0.5-0.7, 0.6-0.7, 0.1-0.6, 0.2-0.6, 0.3-0.6, 0.4-0.6, 0.5-0.6, 0.1-0.5, 0.2-0.5, 0.3-0.5, 0.4-0.5, 0.1-0.4, 0.2-0.4, 0.3-0.4, 0.1-0.3, or 0.2-0.3 dL / g (determined at 25°C using a 0.5 wt% solution in 60 / 40 phenol / 1,1,2,2-tetrachloroethane).

[0137] In another embodiment, based on the total weight of (a) and (b), the coating composition of the present invention comprises 50 wt% to 90 wt% of the polyester polyol (a) and 10 wt% to 50 wt% of the crosslinking agent (b). In some embodiments, based on the total weight of (a) and (b), the polyester polyol (a) is 55wt%-85wt%, 60wt%-80wt%, 65wt%-85wt%, 65wt%-80wt%, 65wt%-75wt%, 70wt%-90wt%, 70wt%-85wt%, 70wt%-80wt%, 75wt%-85wt%, 80wt%-90wt%, or 80wt%-85wt%; and the crosslinking agent (b) is 15wt%-45wt%, 20wt%-40wt%, 15wt%-35wt%, 20wt%-35wt%, 25wt%-35wt%, 10wt%-30wt%, 15wt%-30wt%, 20wt%-30wt%, 15wt%-25wt%, 10wt%-20wt%, or 15wt%-20wt%.

[0138] The crosslinking agent (b) is one or more crosslinking agents selected from the group consisting of: methyl phenolic resins, isocyanates, and amino resin crosslinking agents, or mixtures thereof. Ideally, the crosslinking agent is a methyl phenolic resin, or an isocyanate, or a mixture thereof.

[0139] The methyl phenolic resin contains residues of unsubstituted phenols and / or meta-substituted phenols. These specific methyl phenolic resins exhibit good reactivity with the polyester polyol (a). Desiredly, based on the weight of all crosslinking agent compounds in the resin, the amount of methyl phenolic resin is at least 50 wt%, or greater than 60 wt%, or greater than 70 wt%, or greater than 80 wt%, or greater than 90 wt%.

[0140] The methyl phenolic resin present in the crosslinking composition contains a hydroxymethyl group on the phenolic ring. Phenolic resins with hydroxymethyl functionality are referred to as methyl phenolic resins. As is known in the art, the hydroxymethyl group (--CH2OH) can be etherified with an alcohol and present as --CH2OR, where R is a C1-C8 alkyl group, to improve resin properties such as storage stability and compatibility. For descriptive purposes, the term "hydroxymethyl" as used herein includes both --CH2OH and --CH2OR, and the unsubstituted hydroxymethyl group is CH2OH. The hydroxymethyl group (--CH2OH or --CH2OR) is an end group attached to the methyl phenolic resin. The hydroxymethyl group is formed during the synthesis of the methyl phenolic resin and can further react with another molecule to form an ether or methylene bond, thereby forming a macromolecule.

[0141] Phenolic resins contain residues of unsubstituted or meta-substituted phenols. When preparing methyl phenolic resins from phenols or meta-substituted phenols, both para and ortho positions can be used for bridging reactions to form a branched network, wherein the final hydroxymethyl terminal group on the resin is in the para or ortho position relative to the phenolic hydroxyl group. To prepare methyl phenolic resins, a phenolic composition is used as the starting material. The phenolic composition contains unsubstituted and / or meta-substituted phenols. Based on the weight of the phenolic composition used as the starting material, the amount of unsubstituted, meta-substituted, or a combination of both present in the phenolic composition used as a reactant to prepare the methyl phenolic resin is at least 50 wt%, or at least 60 wt%, or at least 70 wt%, or at least 75 wt%, or at least 80 wt%, or at least 85 wt%, or at least 90 wt%, or at least 95 wt%, or at least 98 wt%.

[0142] The phenolic composition is reacted with a reactive compound, such as an aldehyde, in the following aldehyde:phenol molar ratio (using aldehyde as an example): greater than 1:1, or at least 1.05:1, or at least 1.1:1, or at least 1.2:1, or at least 1.25:1, or at least 1.3:1, or at least 1.35:1, or at least 1.4:1, or at least 1.45:1, or at least 1.5:1, or at least 1.55:1, or at least 1.6:1, or at least 1.65:1, or at least 1.7:1, or at least 1.75:1, or at least 1.8:1, or at least 1.85:1, or at least 1.9:1, or at least 1.95:1, or at least 2:1. There is no upper limit to the amount of aldehyde, which can be up to 30:1, but typically at most 5:1, or at most 4:1, or at most 3:1, or at most 2.5:1. Typically, the aldehyde:phenol ratio is at least 1.2:1 or greater, or 1.4:1 or greater, or 1.5:1 or greater, and usually at most 3:1. Ideally, these ratios also apply to the ratio of aldehyde to unsubstituted phenol or meta-substituted phenol.

[0143] Each phenolic hydroxyl group in a methyl phenolic resin may contain an average of at least 0.3, or at least 0.4, or at least 0.45, or at least 0.5, or at least 0.6, or at least 0.8, or at least 0.9 hydroxymethyl groups, and "hydroxymethyl" includes both --CH2OH and --CH2OR.

[0144] Phenolic resins are obtained by the condensation of phenol with an aldehyde of the general formula (RCHO)n, where R is hydrogen or a hydrocarbon group having 1-8 carbon atoms, and n is 1, 2, or 3. Examples include formaldehyde, metaldehyde, acetaldehyde, glyoxal, propionaldehyde, furfural, or benzaldehyde. Ideally, phenolic resins are the reaction products of phenol and formaldehyde.

[0145] (b) At least a portion of the crosslinking agent comprises a methyl phenolic resin, which is prepared by reacting an unsubstituted phenol or a meta-substituted phenol, or a combination thereof, with an aldehyde. The unsubstituted phenol is phenol (C6H5OH). Examples of meta-substituted phenols include m-cresol, m-ethylphenol, m-propylphenol, m-butylphenol, m-octylphenol, m-alkylphenol, m-phenylphenol, m-alkoxyphenol, 3,5-xylenol, 3,5-diethylphenol, 3,5-dibutylphenol, 3,5-dialkylphenol, 3,5-dicyclohexylphenol, 3,5-dimethoxyphenol, 3-alkyl-5-alkoxyphenol, etc.

[0146] Although other substituted phenolic compounds may be used in combination with the unsubstituted or meta-substituted phenols to prepare phenolic resins, it is desirable that at least 50%, or at least 70%, or at least 80%, or at least 90%, or at least 95%, or at least 98%, or at least 100% of the phenolic compounds used to prepare methyl phenolic resins are unsubstituted or meta-substituted phenols.

[0147] In one aspect, the methyl phenolic resin used in this invention contains meta-substituted phenolic residues.

[0148] Examples of suitable commercial phenolic resins include, but are not limited to, those available from Allenx. PR516 / 60B (based on cresol and formaldehyde), also available from Allenx PR 371 / 70B (based on unsubstituted phenol and formaldehyde) and CURAPHEN 40-856 B60 (based on m-cresol, p-cresol and formaldehyde), available from Bitrez.

[0149] Phenolic resins are ideally thermosetting. Ideally, phenolic resins are not prepared by adding bisphenol A, F, or S (collectively referred to as "BPA").

[0150] Ideally, methyl phenolic resins are alcohol-soluble. They can be liquid at 25°C. The weight-average molecular weight of methyl phenolic resins can range from 200 to 2000, typically 300 to 1000, 400 to 800, or 500 to 600.

[0151] The isocyanate crosslinking agent suitable for use in this invention can be a capped or uncapped isocyanate type. Examples of suitable isocyanate crosslinking agents include, but are not limited to, 1,6-hexamethylene diisocyanate, methylene bis(4-cyclohexyl isocyanate), and isophorone diisocyanate. Ideally, the isocyanate crosslinking agent is isophorone diisocyanate (IPDI) or capped IPDI, which can be obtained from COVESTRO. Obtained in BL 2078 / 2.

[0152] In some embodiments, the crosslinking agent (b) is a mixture of CURAPHEN 40-856B60, which is available from Bitrez, and isophorone diisocyanate (IPDI).

[0153] In another embodiment, the crosslinking agent (b) is a mixture of 70wt%-90wt% of a methyl phenolic resin and 10wt%-30wt% of an isocyanate based on the total weight of the crosslinking agent.

[0154] In addition to methyl phenolic resins and isocyanates, the crosslinking agent (b) can also be an amino resin. The amino resin crosslinking agent (or crosslinking agent) can be a melamine-formaldehyde type or a benzoguanamine-formaldehyde type crosslinking agent, i.e., having multiple -N(CH2OR) crosslinking agents. 3 Crosslinking agents with 2 functional groups, wherein R 3 It is a C1-C4 alkyl group, preferably methyl.

[0155] In yet another embodiment, the crosslinking agent (b) is a mixture of 50 wt% to 70 wt% of an amino resin and 30 wt% to 50 wt% of an isocyanate based on the total weight of the crosslinking agent.

[0156] Typically, the amino crosslinking agent can be selected from compounds of the following formula, where R 3 Independently C1-C4 alkyl:

[0157]

[0158] Amino-containing crosslinking agents are ideally hexamethoxymethyl melamine, hexabutoxymethyl melamine, tetramethoxymethyl benzoguanamine, tetrabutoxymethyl benzoguanamine, tetramethoxymethylurea, and mixed butoxy / methoxy substituted melamines.

[0159] Ideally, in all types of thermosetting compositions, the crosslinking agent composition contains greater than 50 wt%, or greater than 60 wt%, or greater than 70 wt%, or greater than 80 wt%, or greater than 90 wt% of a methyl phenolic resin, based on the weight of the crosslinking agent composition. Alternatively, the remaining crosslinking compounds in the crosslinking composition (if any) are amine-based crosslinking compounds and / or isocyanate crosslinking agents as described above.

[0160] Any thermosetting composition of the present invention may further comprise one or more crosslinking catalysts. Representative crosslinking catalysts include carboxylic acids, sulfonic acids, tertiary amines, tertiary phosphines, tin compounds, or combinations thereof. Some specific examples of crosslinking catalysts include p-toluenesulfonic acid, phosphoric acid, and NACURE, sold by King Industries. TMCatalysts 155, 5076, 1051 and XC-296B, BYK450 and 470, available from BYK-Chemie USA, contain methyltoluenesulfonylimide, p-toluenesulfonic acid, dodecylbenzenesulfonic acid, dinonylnaphthalenesulfonic acid and dinonylnaphthalenedisulfonic acid, benzoic acid, triphenylphosphine, dibutyltin dilaurate and dibutyltin diacetate.

[0161] The crosslinking catalyst used in this invention may depend on the type of crosslinking agent used in the coating composition. For example, the crosslinking agent may include melamine or "amino" crosslinking agents, and the crosslinking catalyst may include p-toluenesulfonic acid, phosphoric acid, uncapped and capped dodecylbenzenesulfonic acid (hereinafter abbreviated as "DDBSA"), dinonylnaphthalenesulfonic acid (hereinafter abbreviated as "DNNSA"), and dinonylnaphthalenedisulfonic acid (hereinafter abbreviated as "DNNDSA"). Some of these catalysts are commercially available, such as NACURE. TM 155, 5076, 1051, 5225 and XC-296B (available from King Industries), BYK-CATALYSTS TM (Available from BYKChemie USA) and CYCAT TM Catalyst (available from Cytec Surface Specialties). The coating compositions of the present invention may contain one or more isocyanate crosslinking catalysts, such as FASCAT. TM 4202 (Dibutyltin dilaurate), FASCAT TM 4200 (dibutyltin diacetate, both available from Arkema), DABCO TM T-12 (available from Air Products) and K-KAT TM 348, 4205, 5218, XC-6212 TM Non-tin catalysts (available from King Industries) and tertiary amines.

[0162] Based on the total weight of any of the above-described curable polyester resin and crosslinking agent compositions, the coating composition may contain an amount of acid or base catalyst ranging from 0.1 wt% to 2 wt%.

[0163] In another embodiment, the coating composition of the present invention further comprises one or more organic solvents. Suitable organic solvents include xylene, ketones (e.g., methylpentyl ketone), 2-butoxyethanol, ethyl 3-ethoxypropionate, toluene, butanol, cyclopentanone, cyclohexanone, ethyl acetate, butyl acetate, Aromatic 100, and Aromatic 150 (both available from ExxonMobil) and other volatile inert solvents commonly used in industrial baking (i.e., thermosetting) enamels, mineral oil, naphtha, toluene, acetone, methyl ethyl ketone, methyl isopentyl ketone, isobutyl acetate, tert-butyl acetate, n-propyl acetate, isopropyl acetate, methyl acetate, ethanol, n-propanol, isopropanol, sec-butanol, isobutanol, ethylene glycol monobutyl ether, propylene glycol n-butyl ether, propylene glycol methyl ether, propylene glycol monopropyl ether, dipropylene glycol methyl ether, diethylene glycol monobutyl ether, trimethylpentanediol monoisobutyrate, ethylene glycol monooctyl ether, diacetone alcohol, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate (available from Eastman Chemical Company under the trademark TEXANOL) TM (obtained through commercial purchase), or a combination thereof.

[0164] Based on the weight of the solvent-containing coating composition, the amount of solvent is ideally at least 20 wt%, or at least 25 wt%, or at least 30 wt%, or at least 35 wt%, or at least 40 wt%, or at least 45 wt%, or at least 50 wt%, or at least 55 wt%. Additionally, or alternatively, the amount of organic solvent may be up to 85 wt% based on the weight of the coating composition.

[0165] In some embodiments of the invention, the coating has the following solvent resistance as measured by the ASTM D7835 method: greater than 50 MEK bifriction, or greater than 70 MEK bifriction, or greater than 90 MEK bifriction, or greater than 100 MEK bifriction, or 50 to 100, 70 to 100, or 90 to 100 MEK bifriction.

[0166] In some embodiments of the invention, the coating has a wedge bending resistance of 70-100, 75-100, or 80-100, as measured by the method of ASTM D3281.

[0167] In some embodiments of the present invention, the coating has a microcrack resistance rating of 2-5, 2.5-5, or 3-5.

[0168] In some embodiments of the present invention, the total dry distillation resistance rating (%) of the coating is 70-100, 80-100, or 90-100.

[0169] In some embodiments of the invention, the coating’s resistance to 5% acetic acid vapor (%) is 40-100, 50-100, 60-100 or 70-100, measured by the method specified in the Examples section.

[0170] In another embodiment, the present invention provides a coating composition for metal packaging applications, comprising:

[0171] a. Based on the total weight of (a), (b), and (c), 70 wt%–80 wt% of a polyester polyol, which is the reaction product of a monomer comprising:

[0172] i. Based on the total moles of i-iv, 28 mol%-60 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD),

[0173] ii. Based on the total moles of i-iv, 5 mol%-45 mol% of 2-methyl-1,3-propanediol (MP diol),

[0174] iii. Based on the total moles of i-iv, 10 mol%-45 mol% of cyclohexanediethanol (CHDM),

[0175] iv. Based on the total moles of i-iv, 1 mol%-4.5 mol% of trimethylolpropane (TMP),

[0176] v. Based on the total moles of v-vii, 45 mol%-100 mol% of terephthalic acid (TPA),

[0177] vi. Based on the total number of moles of v-vii, the amount of isophthalic acid (IPA) from 0 mol% to 55 mol%, and

[0178] vii. Based on the total molar number of v-vii, the amount of acyclic aliphatic diacids is 0 mol%-15 mol%.

[0179] b. Based on the total weight of (a), (b), and (c), 12wt%–27wt% of methyl phenolic resin, and

[0180] c. Based on the total weight of (a), (b), and (c), 3 wt%–8 wt% of isophorone diisocyanate (IPDI),

[0181] The polyester polyol wherein the glass transition temperature (Tg) is 50 to 110°C, the acid value is 0 to 10 mgKOH / g, the hydroxyl value is 10 to 30 mgKOH / g, the number average molecular weight is 5,000 to 20,000 mgKOH / g, and the weight average molecular weight is 10,000 to 100,000; and the coating wherein the coating has a solvent resistance greater than 80 MEK bi-friction as measured by ASTM D7835 and a wedge bending resistance of 70-100% (qualified) as measured by ASTM D3281.

[0182] In another embodiment, the coating has a microcrack resistance rating of 3.5-5, a total distillation resistance rating of 80-100 (%), and a 5% acetic acid vapor resistance rating of 50-100 (%), measured by the method specified in the Examples section.

[0183] The coating composition may also contain at least one pigment. Typically, the pigment is present in an amount of about 20 wt% to about 60 wt% based on the total weight of the composition. Examples of suitable pigments include titanium dioxide, barite, clay, calcium carbonate, and CI Pigment White 6 (titanium dioxide). For example, solvent-based coating formulations may contain titanium dioxide as a white pigment, which can be obtained from CHEMOURS using Ti-Pure... TM Obtained from R 900.

[0184] Therefore, in another embodiment, the present invention provides a polyester composition for white coatings.

[0185] In another embodiment, the present invention provides a white coating for metal packaging applications, comprising:

[0186] a. Based on the total weight of (a) and (b), 80 wt%–90 wt% of a polyester polyol, which is a reaction product of a monomer comprising:

[0187] i. Based on the total moles of i-iv, 28 mol%-60 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD),

[0188] ii. Based on the total moles of i-iv, 5 mol%-45 mol% of 2-methyl-1,3-propanediol (MP diol),

[0189] iii. Based on the total moles of i-iv, 10 mol%-45 mol% of cyclohexanediethanol (CHDM),

[0190] iv. Based on the total moles of i-iv, 1 mol%-4.5 mol% of trimethylolpropane (TMP),

[0191] v. Based on the total moles of v-vii, 45 mol%-100 mol% of terephthalic acid (TPA),

[0192] vi. Based on the total number of moles of v-vii, the amount of isophthalic acid (IPA) from 0 mol% to 55 mol%, and

[0193] vii. Based on the total molar number of v-vii, the amount of acyclic aliphatic diacids ranging from 0 mol% to 15 mol%, and

[0194] b. Based on the total weight of (a) and (b), 10wt%-20wt% of benzoguanamine formaldehyde resin,

[0195] The coating composition further comprises titanium dioxide pigment, and the polyester polyol has a glass transition temperature (Tg) of 50 to 110°C, an acid value of 0 to 10 mg KOH / g, a hydroxyl value of 10 to 30 mg KOH / g, a number-average molecular weight of 5,000 to 20,000 mg KOH / g, and a weight-average molecular weight of 10,000 to 100,000; and the coating has a solvent resistance of greater than 80 MEK bifriction as measured by ASTM D7835 and a wedge bending resistance (% qualified) of 65-100 as measured by ASTM D3281. In another embodiment, the coating has a total distillation resistance rating (%) of 70-100 and a 5% acetic acid vapor resistance rating (%) of 40-100, measured by the methods specified in the Examples section.

[0196] In yet another embodiment, the present invention provides a white coating with improved coating properties for metal packaging applications, comprising:

[0197] a. Based on the total weight of (a), (b), and (c), 70 wt%–85 wt% of a polyester polyol, which is a reaction product of a monomer comprising:

[0198] i. Based on the total moles of i-iv, 28 mol%-60 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD),

[0199] ii. Based on the total moles of i-iv, 5 mol%-45 mol% of 2-methyl-1,3-propanediol (MP diol),

[0200] iii. Based on the total moles of i-iv, 10 mol%-45 mol% of cyclohexanediethanol (CHDM),

[0201] iv. Based on the total moles of i-iv, 1 mol%-4.5 mol% of trimethylolpropane (TMP),

[0202] v. Based on the total moles of v-vii, 45 mol%-100 mol% of terephthalic acid (TPA),

[0203] vi. Based on the total number of moles of v-vii, the amount of isophthalic acid (IPA) from 0 mol% to 55 mol%, and

[0204] vii. Based on the total molar number of v-vii, the amount of acyclic aliphatic diacids is 0 mol%-15 mol%.

[0205] b. Based on the total weight of (a), (b), and (c), 10wt%–20wt% of benzoguanamine formaldehyde resin, and

[0206] c. Based on the total weight of (a), (b), and (c), 5 wt%–12 wt% of isophorone diisocyanate (IPDI),

[0207] The coating composition further comprises titanium dioxide pigment. The polyester polyol has a glass transition temperature (Tg) of 50 to 110°C, an acid value of 0 to 10 mg KOH / g, a hydroxyl value of 10 to 30 mg KOH / g, a number-average molecular weight of 5,000 to 20,000 mg KOH / g, and a weight-average molecular weight of 10,000 to 100,000. The coating has a solvent resistance of greater than 80 MEK bi-friction as measured by ASTM D7835 and a wedge bending resistance (% qualified) of 75-100 as measured by ASTM D3281. In another embodiment, the coating has a total distillation resistance rating (%) of 80-100 and a 5% acetic acid vapor resistance rating (%) of 60-100, measured by the methods specified in the Examples section.

[0208] Examples of the benzoguanamine formaldehyde resins include n-butylated benzoguanamine resins available from INEORS as Maprenal BF-891 or -892 and methylated benzoguanamine resins available from INEORS as Maprenal BF-984, -986 or -987.

[0209] In another embodiment, the polyester polyol portion of the coating is a reaction product of a monomer selected from the group consisting essentially of:

[0210] i. 2,2,4,4-Tetramethyl-1,3-cyclobutanediol;

[0211] ii. 2-Methyl-1,3-propanediol;

[0212] iii. Cyclohexanediol;

[0213] iv. Trimethylolpropane;

[0214] v. terephthalic acid; and

[0215] vi. Isophthalic acid.

[0216] In another embodiment, the polyester polyol portion of the coating is a reaction product of a monomer selected from the group consisting of:

[0217] i. 2,2,4,4-Tetramethyl-1,3-cyclobutanediol;

[0218] ii. 2-Methyl-1,3-propanediol;

[0219] iii. Cyclohexanediol;

[0220] iv. Trimethylolpropane;

[0221] v. terephthalic acid; and

[0222] vi. Isophthalic acid.

[0223] After formulation, the coating composition can be applied to a substrate or article. Therefore, another aspect of the invention is a molded or shaped article coated with the coating composition of the invention. The substrate can be any common substrate, such as aluminum, tin, steel, or galvanized sheet. The coating composition can be applied to the substrate using techniques known in the art, for example by spraying, scraping, or rolling, applying a wet coating of about 0.1 to about 4 mils (1 mil = 25 μm), or 0.5 to 3, or 0.5 to 2, or 0.5 to 1 mil to the substrate. The coating can be cured at a temperature of about 50°C to about 230°C for about 5 seconds to about 90 minutes and then cooled. Examples of coated articles include metal cans for food and beverages, wherein the interior is coated with the coating composition of the invention.

[0224] In another embodiment, the present invention provides a white coating for metal packaging applications, comprising:

[0225] a. Based on the total weight of (a) and (b), 80 wt%–90 wt% of a polyester polyol, which is a reaction product of a monomer comprising:

[0226] i. Based on the total moles of i-iv, 28 mol%-60 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD),

[0227] ii. Based on the total moles of i-iv, 5 mol%-45 mol% of 2-methyl-1,3-propanediol (MP diol),

[0228] iii. Neopentyl glycol (NPG) in amounts ranging from 10 mol% to 45 mol% based on the total moles of i-iv.

[0229] iv. Based on the total moles of i-iv, 1 mol%-4.5 mol% of trimethylolpropane (TMP),

[0230] v. Based on the total number of moles of v-vii, 80 mol%-100 mol% of terephthalic acid (TPA),

[0231] vi. Based on the total number of moles of v-vii, the amount of isophthalic acid (IPA) from 0 mol% to 20 mol%, and

[0232] vii. Based on the total molar number of v-vii, the amount of acyclic aliphatic diacids from 0 mol% to 15 mol%, and

[0233] b. Based on the total weight of (a) and (b), 10wt%-20wt% of benzoguanamine formaldehyde resin,

[0234] The coating composition further comprises titanium dioxide pigment, and the polyester polyol has a glass transition temperature (Tg) of 50 to 110°C, an acid value of 0 to 10 mg KOH / g, a hydroxyl value of 10 to 30 mg KOH / g, a number-average molecular weight of 5,000 to 20,000 mg KOH / g, and a weight-average molecular weight of 10,000 to 100,000; and the coating has a solvent resistance of greater than 80 MEK bi-friction as measured by ASTM D7835 and a wedge bending resistance of 65-100% as measured by ASTM D3281 (% qualified).

[0235] In yet another embodiment, the present invention provides a white coating with improved coating properties for metal packaging applications, comprising:

[0236] a. Based on the total weight of (a), (b), and (c), 70 wt%–85 wt% of a polyester polyol, which is a reaction product of a monomer comprising:

[0237] i. Based on the total moles of i-iv, 28 mol%-60 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD),

[0238] ii. Based on the total moles of i-iv, 5 mol%-45 mol% of 2-methyl-1,3-propanediol (MP diol),

[0239] iii. Neopentyl glycol (NPG) in amounts ranging from 10 mol% to 45 mol% based on the total moles of i-iv.

[0240] iv. Based on the total moles of i-iv, 1 mol%-4.5 mol% of trimethylolpropane (TMP),

[0241] v. Based on the total number of moles of v-vii, 80 mol%-100 mol% of terephthalic acid (TPA),

[0242] vi. Based on the total number of moles of v-vii, the amount of isophthalic acid (IPA) from 0 mol% to 20 mol%, and

[0243] vii. Based on the total molar number of v-vii, the amount of acyclic aliphatic diacids is 0 mol%-15 mol%.

[0244] b. Based on the total weight of (a), (b), and (c), 10wt%–20wt% of benzoguanamine formaldehyde resin, and

[0245] c. Based on the total weight of (a), (b), and (c), 5 wt%–12 wt% of isophorone diisocyanate (IPDI),

[0246] The coating composition further comprises titanium dioxide pigment. The polyester polyol has a glass transition temperature (Tg) of 50 to 110°C, an acid value of 0 to 10 mg KOH / g, a hydroxyl value of 10 to 30 mg KOH / g, a number-average molecular weight of 5,000 to 20,000 mg KOH / g, and a weight-average molecular weight of 10,000 to 100,000. The coating also exhibits solvent resistance greater than 80 MEK bi-friction as measured by ASTM D7835 and wedge bending resistance (% qualified) of 75-100 as measured by ASTM D3281.

[0247] In yet another embodiment, the present invention provides a coating with improved coating properties for metal packaging applications, comprising:

[0248] a. Based on the total weight of (a), (b), and (c), 70 wt%–80 wt% of a polyester polyol, which is the reaction product of a monomer comprising:

[0249] i. Based on the total moles of i-iv, 28 mol%-60 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD),

[0250] ii. Based on the total moles of i-iv, 5 mol%-45 mol% of 2-methyl-1,3-propanediol (MP diol),

[0251] iii. Neopentyl glycol (NPG) in amounts ranging from 10 mol% to 45 mol% based on the total moles of i-iv.

[0252] iv. Based on the total moles of i-iv, 1 mol%-4.5 mol% of trimethylolpropane (TMP),

[0253] v. Based on the total number of moles of v-vii, 80 mol%-100 mol% of terephthalic acid (TPA),

[0254] vi. Based on the total number of moles of v-vii, the amount of isophthalic acid (IPA) from 0 mol% to 20 mol%, and

[0255] vii. Based on the total molar number of v-vii, the amount of acyclic aliphatic diacids is 0 mol%-15 mol%.

[0256] b. Based on the total weight of (a), (b), and (c), 12wt%–27wt% of methyl phenolic resin, and

[0257] c. Based on the total weight of (a), (b), and (c), 3 wt%–8 wt% of isophorone diisocyanate (IPDI),

[0258] The polyester polyol wherein the glass transition temperature (Tg) is 50 to 110°C, the acid value is 0 to 10 mgKOH / g, the hydroxyl value is 10 to 30 mgKOH / g, the number average molecular weight is 5,000 to 20,000 mgKOH / g, and the weight average molecular weight is 10,000 to 100,000; and the coating wherein the coating has a solvent resistance greater than 80 MEK bi-friction as measured by ASTM D7835 and a wedge bending resistance of 70-100% (qualified) as measured by ASTM D3281.

[0259] Therefore, the present invention also provides an article of which at least a portion is coated with the coating composition of the present invention.

[0260] Example

[0261] The present invention can be further illustrated by the following examples, but it should be understood that, unless otherwise expressly stated, these examples are included for illustrative purposes only and are not intended to limit the scope of the invention.

[0262] abbreviation:

[0263] mL is milliliters; wt% is weight percentage; eq is equivalent; hrs or h is hours; mm is millimeters; m is meters; ℃ is degrees Celsius; min is minutes; g is grams; mmol is millimoles; mol is moles; kg is kilograms; L is liters; w / v is weight / volume; μL is microliters; MW is molecular weight.

[0264] Coating testing methods:

[0265] Substrate, preparation of coated test plates, film weight

[0266] Two electroplated tin (ETP) substrates were used. One substrate was from Lakeside Metals Inc. – 0.23mm thick, 2.2g / m³. 2 The tin content, tempering, and annealing type are T61CA. The other board is from Reynolds Metals Company—0.19mm thick, 2.2g / m². 2 The tin content, tempering, and annealing type are DR-8CA. The board is coated with a formulation by casting a wet film using a wire-wound bar, with RDS 14 for coloring and RDS 10 for gold (RDS 14 and RDS 10 are available from RD Specialties, Inc.). This produces a final dry film weight of approximately 14-16 g / m² for the coloring coating. 2 For coatings containing phenolic resin crosslinking agents, the concentration is approximately 6-8 g / m³. 2 Upon curing, it displays a golden color (gold paint). For microcrack testing, the formulation was applied as a wet film by casting with a wire-wound rod-RDS5 (available from RD Specialties, Inc.), yielding 3.0-3.5 g / m². 2 The dry film weight of the applied coating was determined. The cast plate was placed vertically in a support. The Despatch forced air oven was preheated to 203°C. The coated plate was then placed in the oven for an 18-minute baking cycle to allow the coating to bake at a peak metallographic temperature (PMT) of 200°C for 10 minutes. At the end of the baking cycle, the plate support was removed from the oven and allowed to cool to ambient temperature. The dry film weight of the applied coating was determined using a Sencon SI9600 coating thickness gauge.

[0267] wedge bend

[0268] Cut a 1.5-inch wide x 4-inch long specimen from the coated plate. Test the specimen using a Gardco combined bending and impact testing machine according to ASTM D 3281. For the bending test, first bend the coated specimen on a 1 / 8-inch (0.32 cm) steel strip. Place the bent specimen between the butt hinge sections. The hinge, made of two steel blocks, is attached to a base below the conduit. When the hinge is closed, it creates a wedge-shaped gap between the upper and lower sections, ranging from 1 / 8 inch at the hinged end to zero thickness at the free end. Then, drop a flat-down impact tool from a height of one or two feet onto the upper part of the hinge. Once the coated specimen is bent and impacted into a wedge shape, immerse it in an acidified copper sulfate solution (5 wt% copper sulfate, 15 wt% hydrochloric acid (35%), 80 wt% distilled water) for 5 minutes to make any cracks in the coating visible. Remove excess copper sulfate solution by washing with water and patting dry with a towel. Wedge bending failure (mm), measured using a ruler and a luminous magnifying glass, is defined as the total length of a continuous crack along the bending edge of the specimen. The result is reported as the acceptable percentage of wedge bending, which is calculated as follows:

[0269]

[0270] In this experiment, each pass rate for the wedge bending was the average of three repeated tests.

[0271] Methyl ethyl ketone (MEK) double friction

[0272] Resistance to MEK solvents was measured using a MEK friction tester (Gardco MEK Friction Tester AB-410103 EN with a 1 kg block). The test was performed according to a method similar to ASTM D7835. MEK solvent resistance was reported as the number of double friction cycles the coated board could withstand before the coating began to be removed. For example, one round trip constitutes one double friction cycle. The upper limit for each evaluation was set at a maximum of 100 double friction cycles.

[0273] Sterilization resistance test

[0274] A 2.5-inch wide x 4-inch long coated sample was cut from the coated plate. The sample was then placed in a 16-ounce wide-mouthed Le Parfait glass jar, half of which contained food simulants, with one half of the sample above the food simulant liquid and the other half immersed in it. Two different food simulants were evaluated:

[0275] • Lactic acid: 2% lactic acid, 98% deionized water.

[0276] Acetic acid: 3% acetic acid, 97% deionized water.

[0277] Place the appropriately sealed container in an autoclave (Priorcave Model PNA / QCS / EH150) and incubate at 131°C for 1 hour. Once the pyrolysis process is complete, reduce the pressure in the autoclave to ambient conditions. After completing the sterilization cycle, remove the glass container containing the sample from the autoclave. Remove the sample from the container, wash with water, and blot dry with paper towels. Rating the pyrolysis performance from 0 (worst) to 5 (best) using visual inspection. For each food simulant, the pyrolysis performance was rated according to (1) redness in the gas phase, (2) redness in the liquid phase, (3) roughness in the gas phase, (4) roughness in the liquid phase, and (5) cross-cut adhesion in the liquid phase (according to ASTM D3359). The total pyrolysis performance is reported as total pyrolysis %, calculated as follows:

[0278]

[0279] Each distillation grade in this experiment is the average grade from two repeated experiments.

[0280] 5% acetic acid vapor test

[0281] For testing, can ends (with #307 can end size) were manufactured from coated plates prepared by standard methods and membrane weight. Rubber O-rings were fitted to the opposite areas of the manufactured can ends, and the can ends with coating on the inside were then used as lids and properly sealed on top of 16-ounce wide-mouth Le Parfait glass jars filled with 5% acetic acid food simulant (5% acetic acid, 95% deionized water). As with the sterilization test, the properly sealed jars were placed in an autoclave (Priorcave Model PNA / QCS / EH150) and incubated at 131°C for 1 hour. Once the distillation process was complete, the autoclave was depressurized to ambient conditions. The glass jars with coated can ends were then removed from the autoclave. The can ends were removed from the jars, washed with water, and blotted dry with paper towels. Several evaluations were performed in the following order:

[0282] • Enameling is performed on the can end after this process.

[0283] The roughness of the ring is rated from 0 (worst) to 5 (best).

[0284] • Conduct an adhesion test on the can end (according to ASTM D3359). Visually assess adhesion on flat areas and at the ring, rating it from 0 (worst) to 5 (best). The adhesion rating is the average of the adhesion ratings for flat areas and at the ring.

[0285] • The total 5% acetic acid vapor test performance report is the total vapor percentage, calculated as follows:

[0286]

[0287] Microcrack test

[0288] To conduct microcrack testing, a beaded pattern was created on the coated plate to simulate the manufacturing process of a metal can. For example... Figure 1 As shown, a 1-inch × 4-inch coated plate (40) was inserted into the gap between two rollers (10a and 10b) of a modified metal bead roller and then deformed as it passed through the rollers. Under the action of a die, the two rollers, each with a large number of beaded corrugations (20 and 30), replicated beaded patterns (50 and 60) from a range of can sizes (4 oz to 3 kg). The gap between the rollers was adjusted according to the thickness of the tinplate. The film weight of the coating used in this test was 3.0–3.5 g / m³. 2 Within the range. After the beading process, uncoated areas of the board, including the edges and back, were covered with vinyl tape (yellow heat-treated 3M471) and then immersed in an acidified copper sulfate solution for 45 minutes. This solution stained any areas where cracks or microcracks occurred in the coating due to the process. The acidified copper sulfate solution used in the experiment consisted of 16 wt% copper sulfate, 5 wt% hydrochloric acid (35%), and 79 wt% distilled water. All samples were removed from the copper sulfate solution, rinsed with water, dried with paper towels, and the staining was evaluated on a scale of 1 to 5, where 5 was 0% stained area, 1 was ≥50% stained area, and the grade interval was 0.5 for every 5% change in stained area. Each microcrack test grade in this experiment was the average grade of two replicate tests.

[0289] Example 1: Synthesis of polyester polyol (resin 1)

[0290] Polyols were produced using a resin-refined reactor controlled by automated control software. Compositions were prepared in 3.5 mol scales using a 2L vessel with a top stirrer and a partial condenser with a top total condenser and a Dean Stark water separator. An azeotropic solvent (A150ND, available from ExxonMobil) of approximately 10 wt% (based on reaction yield) of high-boiling Aromatic 150 ND was used to facilitate the removal of water condensate from the reaction mixture, and a standard paddle stirrer was used to prevent the reaction mixture from becoming too viscous. Isophthalic acid (IPA), terephthalic acid (TPA), adipic acid (AD), 1,4-cyclohexanediol (CHDM), 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD), 2-methyl-1,3-propanediol (MPdiol), trimethylolpropane (TMP), and Aromatic 150 were added to the reactor. After assembling and covering the reactor with nitrogen, Fascat 4100 (monobutyltin oxide, available from PMC Organmetallix Inc.) was added through a sampling port. Additional A150 / A150ND solvent was added to the Dean Stark separator to maintain a solvent level of approximately 10 wt% in the reactor. The reaction mixture was heated from room temperature to 150°C without stirring, using the set output controlled by the automated system. Once the reaction mixture was fluid, stirring was initiated to promote uniform heating of the mixture. At 150°C, the heating control was switched to automatic control, and the temperature was increased to 230°C over 4 hours. The reaction was held at 230°C for 1 hour, then heated to 240°C over 1 hour. The reaction was then held at 240°C, and samples were taken every 1–2 hours after clarification until the desired acid value was reached (approximately 8 hours). The reaction mixture was then further diluted with A150ND, targeting a solids weight percentage of 55%. The solution was filtered through an approximately 250 μm paint filter before use for formulation and application testing. It should be noted that the diol excess is determined based on experience with laboratory reactors and may vary depending on the partial condenser and reactor design used. The diol:acid ratio is also controlled to achieve the same molecular weight with simpler variations in acid and hydroxyl end-group content.

[0291]

[0292]

[0293] Example 2: Synthesis of polyester polyols (resins 2, 3, 4, and 5)

[0294] Resins 2-5 were also synthesized using the same method described above. Table 1 lists the composition of resins 1-5, and Table 2 lists their resin properties.

[0295] Glass transition temperature (Tg) was determined using a Q2000 differential scanning calorimeter (DSC) from TA Instruments in Newcastle, Delaware, USA, at a scan rate of 20 °C / min. Number-average molecular weight (Mn) and weight-average molecular weight (Mw) were determined by gel permeation chromatography (GPC) using polystyrene equivalent molecular weight. Acid value was measured using a procedure based on ASTM D7253-1 entitled "Standard Test Method for Polyurethane Raw Materials: Determination of Acidity of Polyether Polyols," and hydroxyl value was measured using a procedure based on ASTM E222-1 entitled "Standard Test Method for Hydroxyl Groups Using Acetic Anhydride."

[0296] Table 1. Synthetic Polyester Polyols

[0297]

[0298]

[0299] Table 2. Resin properties of polyester polyols

[0300] Resin 1 96 13866 70582 3 21 Resin 2 81 11636 33116 3 19 Resin 3 85 11509 38195 5 16 Resin 4 87 15292 45074 3 11 Resin 5 75 11390 38325 5 12

[0301] Comparative Example 1: Synthesis of Polyester Polyol (Comparative Resin CR-1)

[0302] This example describes the synthesis of a polyester polyol having higher 1,4-CHDM (50 mol%), higher TMP (8 mol%), and higher hydroxyl value (52.4 mg KOH / g) compared to the polyester polyol of the present invention.

[0303] Polyols were prepared using a resin reactor apparatus controlled by automated control software. Compositions were prepared in a 3.5 mol scale using a 2 L reactor with a top stirrer and a partial condenser with a top total condenser and a Dean Stark water separator. Approximately 10 wt% (based on reaction yield) of high-boiling-point azeotropic solvents (A150 and A150ND) were used to facilitate the removal of water condensate from the reaction mixture, and a standard paddle stirrer was used to prevent the reaction mixture from becoming viscous. Isophthalic acid (IPA), terephthalic acid (TPA), adipic acid (AD), 1,4-cyclohexanediol (CHDM), 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD), 2-methyl-1,3-propanediol (MPdiol), trimethylolpropane (TMP), and Aromatic 150 were added to the reactor. After assembling the reactor and covering it with nitrogen, Fascat 4100 (monobutyltin oxide) was added through a sampling port. Additional A150 / A150ND solvent was added to the Dean Stark separator to maintain a solvent level of approximately 10 wt% in the reactor. The reaction mixture was heated from room temperature to 150°C without stirring, using the set output controlled by the automated system. Once the reaction mixture was fluid, stirring was initiated to promote uniform heating of the mixture. At 150°C, heating control was switched to automatic control, and the temperature was increased to 230°C over 4 hours. The reaction was held at 230°C for 1 hour, and samples were taken every 1–2 hours after clarification until the desired acid value was reached (approximately 6 hours). The reaction mixture was then further diluted with A150ND, targeting a solids weight percentage of 55%. The solution was filtered through an approximately 250 μm paint filter before use for formulation and application testing. It should be noted that the glycol excess was determined based on experience with laboratory reactors and may vary depending on the partial condenser and reactor design used. The glycol:acid ratio was also controlled to achieve the same molecular weight with simpler variations in acid and hydroxyl end-group content.

[0304]

[0305] Comparative Example 2: Synthesis of Polyester Polyol (CR-2)

[0306] This embodiment describes the synthesis of a polyester polyol with higher TMP (4.7 mol%) and higher hydroxyl value (59 mg KOH / g) compared to the polyester polyol of the present invention.

[0307] Polyols were prepared using a resin-refined reactor apparatus controlled by automated control software. Compositions were prepared in a 3.5 mol scale using a 2 L vessel with a top stirrer and a partial condenser with a top total condenser and a Dean Stark water separator. Approximately 10 wt% (based on reaction yield) of high-boiling-point azeotropic solvents (A150 and A150ND) were used to facilitate the removal of water condensate from the reaction mixture, and a standard paddle stirrer was used to maintain the viscosity of the reaction mixture at a reasonable level. Isophthalic acid (IPA), terephthalic acid (TPA), adipic acid (AD), 1,4-cyclohexanediol (CHDM), 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD), 2-methyl-1,3-propanediol (MP-diol), trimethylolpropane (TMP), and Aromatic 150 were added to the reactor, which was then fully assembled. Fascat 4100 (monobutyltin oxide) was added through a sampling port and the reactor was covered with nitrogen to initiate the reaction. Additional A150 / A150ND solvent was added to the Dean Stark separator to maintain a solvent level of approximately 10 wt% in the reactor. The reaction mixture was heated from room temperature to 150°C without stirring, using the set output controlled by the automated system. Once the reaction mixture was sufficiently fluid, stirring was initiated to promote uniform heating of the mixture. At 150°C, the heating control was switched to automatic control, and the temperature was increased to 230°C over 4 hours. The reaction was held at 230°C for 1 hour, and samples were taken every 1–2 hours after clarification until the desired acid value was reached (approximately 6 hours). The reaction mixture was then further diluted with A150ND, targeting a solids weight percentage of 55%. The solution was filtered through an approximately 250 μm paint filter before use for formulation and application testing. It should be noted that the glycol excess was determined based on experience with laboratory reactors and may vary depending on the partial condenser and reactor design used. The glycol:acid ratio was also controlled to achieve the same molecular weight with simpler variations in acid and hydroxyl end-group content.

[0308]

[0309]

[0310] Comparative Example 3: Synthesis of Polyester Polyol (CR-3)

[0311] This example describes the synthesis of a polyester polyol having higher adipic acid content (25 mol%) and higher 1,4-CHDM content (50 mol%) compared to the polyester polyol of the present invention.

[0312] Polyols were prepared using a resin reactor apparatus controlled by automated control software. Compositions were prepared in a 3.5 mol scale using a 2 L reactor with a top stirrer and a partial condenser with a top total condenser and a Dean Stark water separator. Approximately 10 wt% (based on reaction yield) of high-boiling-point azeotropic solvents (A150 and A150ND) were used to facilitate the removal of water condensate from the reaction mixture, and a standard paddle stirrer was used to maintain the viscosity of the reaction mixture at a reasonable level. Isophthalic acid (IPA), terephthalic acid (TPA), adipic acid (AD), 1,4-cyclohexanediol (CHDM), 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD), 2-methyl-1,3-propanediol (MPdiol), trimethylolpropane (TMP), and Aromatic 150 were added to the reactor, which was then fully assembled. After assembling the reactor and covering it with nitrogen, Fascat 4100 (monobutyltin oxide) was added through a sampling port. Additional A150 / A150ND solvent was added to the Dean Stark separator to maintain a solvent level of approximately 10 wt% in the reactor. The reaction mixture was heated from room temperature to 150°C without stirring, using the set output controlled by the automated system. Once the reaction mixture was sufficiently fluid, stirring was initiated to promote uniform heating of the mixture. At 150°C, heating control was switched to automatic control, and the temperature was increased to 230°C over 4 hours. The reaction was held at 230°C for 1 hour, and samples were taken every 1–2 hours after clarification until the desired acid value was reached (approximately 3 hours). The reaction mixture was then further diluted with A150ND, targeting a solids weight percentage of 55%. The solution was filtered through an approximately 250 μm paint filter before use for formulation and application testing. It should be noted that the glycol excess was determined based on experience with laboratory reactors and may vary depending on the partial condenser and reactor design used. The glycol:acid ratio was also controlled to achieve the same molecular weight with simpler variations in acid and hydroxyl end-group content.

[0313]

[0314] Comparative Example 4: Synthesis of Polyester Polyol (CR-4)

[0315] This embodiment describes the synthesis of a polyester polyol having lower TPA (10 mol%), higher TMP (8 mol%), and higher hydroxyl value (50 mg KOH / g) compared to the polyester polyol of the present invention.

[0316] Polyols were prepared using a resin reactor apparatus controlled by automated control software. Compositions were prepared in a 3.5 mol scale using a 2 L reactor with a top stirrer and a partial condenser with a top total condenser and a Dean Stark water separator. Approximately 10 wt% (based on reaction yield) of high-boiling-point azeotropic solvents (A150 and A150ND) were used to facilitate the removal of water condensate from the reaction mixture, and a standard paddle stirrer was used to maintain the viscosity of the reaction mixture at a reasonable level. Isophthalic acid (IPA), terephthalic acid (TPA), adipic acid (AD), 1,4-cyclohexanediol (CHDM), 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD), 2-methyl-1,3-propanediol (MPdiol), trimethylolpropane (TMP), and Aromatic 150 were added to the reactor, which was then fully assembled. After assembling the reactor and covering it with nitrogen, Fascat 4100 (monobutyltin oxide) was added through a sampling port. Additional A150 / A150ND solvent was added to the Dean Stark separator to maintain a solvent level of approximately 10 wt% in the reactor. The reaction mixture was heated from room temperature to 150°C without stirring, using the set output controlled by the automated system. Once the reaction mixture was sufficiently fluid, stirring was initiated to promote uniform heating of the mixture. At 150°C, the heating control was switched to automatic control, and the temperature was increased to 230°C over 4 hours. The reaction was held at 230°C for 1 hour, and samples were taken every 1–2 hours after clarification until the desired acid value was reached (approximately 2 hours). The reaction mixture was then further diluted with A150ND, targeting a solids weight percentage of 55%. The solution was filtered through an approximately 250 μm paint filter before use for formulation and application testing. It should be noted that the glycol excess was determined based on experience with laboratory reactors and may vary depending on the partial condenser and reactor design used. The glycol:acid ratio was also controlled to achieve the same molecular weight with simpler variations in acid and hydroxyl end-group content.

[0317]

[0318]

[0319] Comparative Example 5: Synthesis of Polyester Polyol (CR-5)

[0320] This example describes the synthesis of a polyester polyol having lower TPA (10 mol%) and higher 1,4-CHDM (50 mol%) compared to the polyester polyol of the present invention.

[0321] Polyols were prepared using a resin reactor apparatus controlled by automated control software. Compositions were prepared in a 3.5 mol scale using a 2L reactor with a top stirrer and a partial condenser with a top total condenser and a Dean Stark water separator. Approximately 10 wt% (based on reaction yield) of high-boiling-point azeotropic solvents (A150 and A150ND) were used to facilitate the removal of water condensate from the reaction mixture, and a standard paddle stirrer was used to maintain the viscosity of the reaction mixture at a reasonable level. Isophthalic acid (IPA), terephthalic acid (TPA), adipic acid (AD), 1,4-cyclohexanediol (CHDM), 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD), 2-methyl-1,3-propanediol (MPdiol), trimethylolpropane (TMP), and Aromatic 150 were added to the reactor, which was then fully assembled. After assembling the reactor and covering it with nitrogen, Fascat 4100 (monobutyltin oxide) was added through a sampling port. Additional A150 / A150ND solvent was added to the Dean Stark separator to maintain a solvent level of approximately 10 wt% in the reactor. The reaction mixture was heated from room temperature to 150°C without stirring, using the set output controlled by the automated system. Once the reaction mixture was sufficiently fluid, stirring was initiated to promote uniform heating of the mixture. At 150°C, the heating control was switched to automatic control, and the temperature was increased to 230°C over 4 hours. The reaction was held at 230°C for 1 hour, and samples were taken every 1–2 hours after clarification until the desired acid value was reached (approximately 4 hours). The reaction mixture was then further diluted with A150ND, targeting a solids weight percentage of 55%. The solution was filtered through an approximately 250 μm paint filter before use for formulation and application testing. It should be noted that the glycol excess was determined based on experience with laboratory reactors and may vary depending on the partial condenser and reactor design used. The glycol:acid ratio was also controlled to achieve the same molecular weight with simpler variations in acid and hydroxyl end-group content.

[0322]

[0323] Comparative Example 6: Resin Properties of Synthesized Comparative Polyester Polyols

[0324] Table 3 lists the composition of the comparative resins (CR-1 to CR-5), and Table 4 lists their resin properties. Glass transition temperature (Tg) was determined using a Q2000 differential scanning calorimeter (DSC) from TA Instruments in Newcastle, Delaware, USA, at a scan rate of 20 °C / min. Number-average molecular weight (Mn) and weight-average molecular weight (Mw) were determined by gel permeation chromatography (GPC) using polystyrene equivalent molecular weight. Acid value was measured using a procedure based on ASTM D7253-1 entitled "Standard Test Method for Polyurethane Raw Materials: Determination of Acidity of Polyether Polyols," and hydroxyl value was measured using a procedure based on ASTM E222-1 entitled "Standard Test Method for Hydroxyl Groups Using Acetic Anhydride."

[0325] Table 3. Comparison of synthesized polyester polyols

[0326]

[0327] Table 4. Resin properties of polyester polyols

[0328] CR-1 70 6053 18844 5 52 CR-2 56 6801 26787 3 42 CR-3 59 5300 11461 3 23 CR-4 73 5946 21330 5 50 CR-5 84 13237 44507 3 15

[0329] Comparative Example 7: Synthesis of Polyester Polyol (Comparative Resin CR-6)

[0330] This example describes the synthesis of polyester polyols by replacing cyclohexanediol with isosorbide.

[0331] Polyols were prepared using a resin-refined reactor apparatus controlled by automated control software. Compositions were prepared in a 3.5 mol scale using a 2L reactor with a top stirrer and a partial condenser with a top total condenser and a Dean Stark water separator. Approximately 10 wt% (based on reaction yield) of high-boiling-point azeotropic solvents (A150 and A150ND) was used to facilitate the removal of water condensate from the reaction mixture, and a standard paddle stirrer was used to maintain the viscosity of the reaction mixture at a reasonable level. IPA, TPA, AD, isosorbide (dihydro-D-glucanol, IBIB), 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD), 2-methyl-1,3-propanediol (MP-diol), trimethylolpropane (TMP), and Aromatic 150 were added to the reactor, which was then fully assembled. After assembling the reactor and covering it with nitrogen, Fascat 4100 (monobutyltin oxide) was added through a sampling port. Add additional A150 / A150ND solvent to the DeanStark separator to maintain a solvent level of approximately 10 wt% in the reactor. Using the set output controlled by the automated system, heat the reaction mixture from room temperature to 150°C without stirring. Once the reaction mixture is sufficiently fluid, begin stirring to promote uniform heating of the mixture. At 150°C, switch the heating control to automatic control and increase the temperature to 230°C over 4 hours. Hold the reaction at 230°C for 1 hour, then heat to 240°C over 1 hour. Maintain the reaction at 240°C and sample every 1–2 hours after clarification until the desired acid value is reached (approximately 8 hours). Further dilute the reaction mixture with A150ND, targeting a solids weight percentage of 55%. Filter the solution through an approximately 250 μm paint filter before use for formulation and application testing. It should be noted that the diol excess is determined based on experience with laboratory reactors and may vary depending on the partial condenser and reactor design used. The ratio of diol to acid is also controlled to achieve the same molecular weight with simpler variations in acid and hydroxyl end-group content.

[0332] The polyester polyol prepared in this way forms a crystalline solid rather than a pourable liquid resin, which makes it unsuitable for use.

[0333]

[0334]

[0335] Comparative Example 8: Synthesis of Polyester Polyol (CR-7)

[0336] This example describes the synthesis of polyester polyols by replacing 1,4-cyclohexanediethanol (1,4-CHDM) with TCDDM. TCDDM is a 4,8-bis(hydroxymethyl)tricyclic [5.2.1.0] 2,6 A mixture of decane isomers. TCDDM is also known as tricyclic decanediethanol and tricyclic [5.2.1.0] 2,6 Decane-4,8-diethanol. TCDDM can be obtained from OQ Chemicals as TCD Alcohol DM.

[0337] Polyols were prepared using a resin reactor apparatus controlled by automated control software. Compositions were prepared in a 3.5 mol scale using a 2 L reactor with a top stirrer and a partial condenser with a top total condenser and a Dean Stark water separator. Approximately 10 wt% (based on reaction yield) of high-boiling-point azeotropic solvents (A150 and A150ND) were used to facilitate the removal of water condensate from the reaction mixture, and a standard paddle stirrer was used to maintain the viscosity of the reaction mixture at a reasonable level. Isophthalic acid (IPA), terephthalic acid (TPA), adipic acid (AD), tricyclodecanediethanol (TCDDM), 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD), 2-methyl-1,3-propanediol (MPdiol), trimethylolpropane (TMP), and Aromatic 150 were added to the reactor, which was then fully assembled. After assembling the reactor and covering it with nitrogen, Fascat 4100 (monobutyltin oxide) was added through a sampling port. Add additional A150 / A150ND solvent to the Dean Stark separator to maintain a solvent level of approximately 10 wt% in the reactor. Using the set output controlled by the automated system, heat the reaction mixture from room temperature to 150°C without stirring. Once the reaction mixture is sufficiently fluid, begin stirring to promote uniform heating of the mixture. At 150°C, switch the heating control to automatic control and increase the temperature to 230°C over 4 hours. Hold the reaction at 230°C for 1 hour, then heat to 240°C over 1 hour. Maintain the reaction at 240°C and sample every 1–2 hours after clarification until the desired acid value is reached (approximately 8 hours). Further dilute the reaction mixture with A150ND, targeting a solids weight percentage of 55%. Filter the solution through an approximately 250 μm paint filter before use for formulation and application testing. It should be noted that the diol excess is determined based on experience with laboratory reactors and may vary depending on the partial condenser and reactor design used. The ratio of diol to acid is also controlled to achieve the same molecular weight with simpler variations in acid and hydroxyl end-group content.

[0338] The resulting polyester polyol had a hydroxyl value of 20 mgKOH / g, an acid value of 5 mgKOH / g, a Tg of 102℃, and Mn and Mw of 10197 g / mol and 35888 g / mol, respectively.

[0339]

[0340] Example 3: Preparation of gold paint formulation (GF1-5 and CGF1-7)

[0341] Coating formulations for gold were prepared using resins 1-5 and comparative resins CR-1 to CR-7. Table 5 lists the gold formulations (GF1-3) prepared using resins 1-5, and Table 6 lists the comparative gold formulations (CGF1-7) prepared using CR1-7.

[0342] Prior to formulation, all polyester polyols were diluted to 50 wt% solids in A150ND. Solvent blends were prepared from a mixture of xylene, butanol, and MAK at 30 wt%, 30 wt%, and 40 wt%, respectively. Empty, lidded glass jars were labeled and pre-weighed to record the tare weight. For each formulation, Curaphen 40-856-B60 was weighed separately. BL2078 / 2 XC-296B and solvent blends were added sequentially to the resin solution. Then, in Dispermat... TM Shear the formulation on a high-speed disperser at 1500 RPM for 10–15 minutes using a Cowles blade. Once complete, then tumble the glass jar containing the formulation overnight under ambient conditions with gentle agitation.

[0343] Choose food-grade approvals available from Covestro AG. BL 2078 / 2 and Curaphen 40-856-B60, available from Bitrez, were selected as crosslinking agents for blocked IPDI trimer and m-cresin phenolic resin, respectively. Food-grade approved products available from King Industries were also chosen. XC-296B is used as an H3PO4 catalyst.

[0344] Table 5. Gold coating formulations based on resins 1-5

[0345]

[0346]

[0347] Table 6. Comparison of gold coating formulations based on CR1-7

[0348]

[0349]

[0350] Example 4: Coating properties of gold formulations (GF 1-3 and CGF 1-7)

[0351] The formulation prepared in Example 3 was applied to a tin plate (available from Lakeside Metals Inc.) with a thickness of 0.23 mm and a density of 2.2 g / m² by casting a wet film using a wire-wound bar-RDS 10 (available from RD Specialties, Inc.). 2 Tin content, tempering and annealing type T61CA (described as Lakesider substrate). This results in a final dry film weight of approximately 6-8 g / m². 2 The cast plate was placed in a holder and held vertically in the oven for curing. The Despatch forced air oven was preheated to a set temperature of 203°C. The coated plate in the holder was then placed in the oven for an 18-minute baking cycle to allow the coating to bake at a peak metallographic temperature (PMT) of 200°C for 10 minutes. At the end of the baking cycle, the plate holder was removed from the oven and allowed to cool to ambient conditions. The dry film weight of the applied coating was determined using a Sencon SI9600 coating thickness gauge. Once the coating was formed, it was subjected to coating performance tests, including MEK double friction, wedge bending, microcracking, sterilization resistance, and 5% acetic acid vapor tests. The test results are listed in Table 7.

[0352] Table 7. Coating characteristics of gold formulations on Lakeside substrates

[0353] GF1 100+ 79% 3.5 94% 80% GF2 100+ 86% 4.5 88% 70% GF3 99 90% 3.75 83% NA CGF1 63 73% 1.5 69% 0% CGF2 100+ 75% 1.0 50% 53% CGF3 46 45% 1.0 59% 28% CGF4 92 68% 1.0 80% 25% CGF5 98 76% 0.5 83% 70% CGF6 100+ 80% 3.0 74% 37% CGF7 99 80% 1.0 98% 80%

[0354] Specifically, formulations GF-2, GF-4, GF-5, and CGF-6 were applied to a tin plate (available from Reynolds Metals Company) with a thickness of 0.19 mm and a density of 2.2 g / m² by casting a wet film using a wire-wound bar-RDS 10 (available from RD Specialties, Inc.). 2 Tin content, tempering and annealing type DR-8CA (described as Reynolds substrate). This produces a final dry film weight of approximately 6-8 g / m². 2The cast plate was placed in a holder and held vertically in the oven for curing. The Despatch forced air oven was preheated to a set temperature of 203°C. The coated plate in the holder was then placed in the oven for an 18-minute baking cycle to allow the coating to bake at a peak metallographic temperature (PMT) of 200°C for 10 minutes. At the end of the baking cycle, the plate holder was removed from the oven and allowed to cool to ambient conditions. The dry film weight of the applied coating was determined using a Sencon SI9600 coating thickness gauge. Once the coating was formed, it was subjected to coating performance tests, including MEK double friction, wedge bending, microcracking, sterilization resistance, and 5% acetic acid vapor tests. The test results are listed in Table 8.

[0355] Table 8. Coating properties of gold formulation on Reynolds substrates

[0356] GF2 100 80% 4.0 95% 70% GF4 100 95% 3.5 96% -- GF5 98 93% 4.0 95% -- CGF6 99 66% 2.5 87% 70%

[0357] Example 5: Preparation of white paint formulations containing amino crosslinking agents (WF1-3 and CWF1-7)

[0358] White coating formulations were prepared using resins 1-3 and comparative resins CR-2 and CR-6. Table 9 lists the white formulations WF-1 to WF-3 prepared from resins 1-3, and the comparative white formulations CWF-1 and CWF-2 prepared from CR-2 and CR-6, respectively.

[0359] Before preparation, all polyester polyols were first diluted to 50 wt% solids in A150ND. Solvent blends were prepared from a mixture of xylene, butanol, and MAK at 30 wt%, 30 wt%, and 40 wt%, respectively. Empty, lidded glass jars were labeled and pre-weighed to record the tare weight. To prepare the pigment paste, a sample of the polyester polyol solution (50 wt%, 27.12 g) was added to the pre-weighed glass jar. Ti Pure™ R900 was then gradually added to the polyester resin solution at a shear rate of 800–1000 RPM using a Cowles blade on a Dispermat™ high-speed disperser. Once all pigment was added, the shear rate was increased to 3000 RPM and maintained for 15 minutes. The remaining components, including the remaining polyester polyol (27.12 g), were then added. 987 -1790 (or -392), 5076 and the solvent blend are added to the formulation while stirring with a laboratory mixer until all components are thoroughly mixed. Once complete, the glass jar containing the formulation is then left to swirl overnight under ambient conditions with gentle stirring.

[0360] Choose food-grade approved products available commercially from Ineos. BF987 is used as a crosslinking agent for benzoguanamine-formaldehyde resins. Choose a food-grade approved product available from King Industries. 5076 was used as the DDBSA catalyst. Food-grade approved Ti-Pure™ R900, available from Chemours, was selected as the TiO2 pigment. [The text then abruptly shifts to a different topic:] [A product] available from BYK was selected. -392 and -1790 is used as a surface additive.

[0361] Table 9. White paint formulations containing amino crosslinking agents

[0362]

[0363] Example 6: Coating properties of white formulations (WF1-3 and CWF1-2)

[0364] The formulation prepared in Example 5 was applied to a tin plate, available from Reynolds Metals Company, by casting a wet film using a wire-wound bar (RDS14) (available from RD Specialties, Inc.). This produces a final dry film weight of approximately 14-16 g / m² for use in coloring coatings. 2 The cast plate was placed in a holder and held vertically in the oven for curing. The Despatch forced air oven was preheated to a set temperature of 203°C. The coated plate in the holder was then placed in the oven for an 18-minute baking cycle to allow the coating to bake at a peak metallographic temperature (PMT) of 200°C for 10 minutes. At the end of the baking cycle, the plate holder was removed from the oven and allowed to cool back to ambient conditions. The dry film weight of the applied coating was determined using a Sencon SI9600 coating thickness gauge. Once the coating was formed, it was subjected to coating performance tests, including MEK double friction, wedge bending, sterilization resistance test, and 5% acetic acid vapor test. The test results are listed in Table 10.

[0365] Table 10. Coating properties of white formulations (WF 1-3 and CWF 1-2) on Reynolds substrates

[0366] WF1 100 68% 90% 40% WF2 100 77% 83% 55% WF3 100 76% 70% 70% CWF1 100 81% 67% 25% CWF2 100 71% 68% 30%

[0367] Example 7: Preparation of white paint formulations containing amino and isocyanate crosslinking agents (WF 4-5 and CWF 3)

[0368] White coating formulations were prepared using resins 1 and 2, as well as comparative resin CR-6. Table 11 lists the white formulations prepared with resins 1-2 and WF-4 to WF-5, and the comparative white formulation CWF-3 prepared with CR-6.

[0369] Before preparation, all polyester polyols were first diluted to 50 wt% solids in A150ND. Solvent blends were prepared from a mixture of xylene, butanol, and MAK at 30 wt%, 30 wt%, and 40 wt%, respectively. Empty, lidded glass jars were labeled and pre-weighed to record the tare weight. To prepare the pigment paste, a sample of the polyester polyol solution (27.12 g, 50 wt%) was added to the pre-weighed glass jar. Ti Pure™ R900 was then gradually added to the polyester resin solution at a shear rate of 800-1000 RPM using a Cowles blade on a Dispermat™ high-speed disperser. Once all pigments were added, the shear rate was increased to 3000 RPM and maintained for 15 minutes. The remaining components, including the remaining polyester polyols (27.12 g), were then added. 987 BL 2078 / 2 -1790 (or -392), 5076 and the solvent blend are added to the formulation while stirring with a laboratory mixer until all components are thoroughly mixed. Once complete, the glass jar containing the formulation is then left to swirl overnight under ambient conditions with gentle stirring.

[0370] Choose from food-grade approved products available commercially from Ineos and Covestro respectively. BF987 and BL 2078 / 2 is used as a crosslinking agent for benzoguanamine-formaldehyde resins and for end-capped IPDI trimer crosslinking. Choose a food-grade approved product available from King Industries. 5076 was used as the DDBSA catalyst. Food-grade approved Ti-Pure™ R900, available from Chemours, was selected as the TiO2 pigment. [The text then abruptly shifts to a different topic:] [A product] available from BYK was selected. -392 and -1790 is used as a surface additive.

[0371] Table 11. White paint formulations containing amino and isocyanate crosslinking agents

[0372]

[0373]

[0374] Example 8: Coating properties of white formulations (WF4-5 and CWF3)

[0375] The formulation prepared in Example 7 was applied to a tin plate, available from Reynolds Metals Company, by casting a wet film using a wire-wound bar (RDS14) (available from RD Specialties, Inc.). This produced a final dry film weight of approximately 14-16 g / m² for use in coloring coatings. 2 The cast plate was placed in a holder and held vertically in the oven for curing. The Despatch forced air oven was preheated to a set temperature of 203°C. The coated plate in the holder was then placed in the oven for an 18-minute baking cycle to allow the coating to bake at a peak metallographic temperature (PMT) of 200°C for 10 minutes. At the end of the baking cycle, the plate holder was removed from the oven and allowed to cool to ambient conditions. The dry film weight of the applied coating was determined using a Sencon SI9600 coating thickness gauge. Once the coating was formed, it was subjected to coating performance tests, including MEK double friction, wedge bending, sterilization resistance test, and 5% acetic acid vapor test. The test results are listed in Table 12.

[0376] Table 12. Coating properties of white formulations (WF4-5 and CWF3) on Reynolds substrates

[0377] WF4 100+ 79% 94% 62% WF5 100+ 80% 90% 63% CWF3 100+ 73% 71% 53%

[0378] As described above, the present invention provides a non-BPA coating composition for metal packaging applications with improved coating properties, comprising:

[0379] a. Polyester polyol, which is a reaction product of a monomer, the monomer comprising:

[0380] i. Based on the total moles of i-iv, 28 mol%-60 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD),

[0381] ii. Based on the total moles of i-iv, 5 mol%-45 mol% of 2-methyl-1,3-propanediol (MP diol),

[0382] iii. Based on the total moles of i-iv, 10 mol%-45 mol% of cyclohexanediethanol (CHDM),

[0383] iv. Based on the total moles of i-iv, 1 mol%-4.5 mol% of trimethylolpropane (TMP),

[0384] v. Based on the total moles of v-vii, 45 mol%-100 mol% of terephthalic acid (TPA),

[0385] vi. Based on the total number of moles of v-vii, the amount of isophthalic acid (IPA) from 0 mol% to 55 mol%, and

[0386] vii. Based on the total molar number of v-vii, the amount of acyclic aliphatic diacids from 0 mol% to 15 mol%, and

[0387] b. One or more crosslinking agents selected from the group consisting of: methyl phenolic resins, isocyanates, and amino resin crosslinking agents.

[0388] The polyester polyol described herein has a glass transition temperature (Tg) of 50 to 110°C, an acid value of 0 to 10 mg KOH / g, a hydroxyl value of 10 to 40 mg KOH / g, a number-average molecular weight of 5,000 to 20,000 mg KOH / g, and a weight-average molecular weight of 10,000 to 100,000; and the coating described herein has a solvent resistance of greater than 50 MEK bi-friction as measured by ASTM D7835 and a wedge bending resistance of 70-100% (qualified) as measured by ASTM D3281. This coating, as a BPA-free coating, has particular applications in inner tank coatings.

[0389] The present invention has been described in detail with reference to the embodiments disclosed herein; however, it should be understood that variations and modifications can be made within the spirit and scope of the invention.

Claims

1. A coating composition for metal packaging, comprising: a. A polyester polyol, which is a reaction product of a monomer, said monomer comprising: i. 28 mol%–60 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol based on the total moles of i–iv. ii. Based on the total moles of i-iv, 5 mol%-45 mol% of 2-methyl-1,3-propanediol, iii. Based on the total moles of i-iv, 10 mol%-45 mol% of cyclohexanediethanol, iv. Based on the total molar number of i-iv, 0.6 mol%-4.5 mol% of trimethylolpropane, v. Based on the total number of moles of v-vii, 45 mol%-100 mol% of terephthalic acid. vi. Based on the total number of moles of v-vii, 0 mol%-55 mol% of isophthalic acid, and vii. Based on the total molar number of v-vii, the amount of acyclic aliphatic diacids ranging from 0 mol% to 15 mol%, and b. At least one crosslinking agent, said crosslinking agent being selected from the group consisting of: methyl phenolic resins, isocyanates, and amino resin crosslinking agents. The polyester polyol wherein the glass transition temperature (Tg) is 50 to 110°C, the acid value is 0 to 10 mgKOH / g, the hydroxyl value is 10 to 40 mgKOH / g, the number average molecular weight is 5,000 to 20,000 mgKOH / g, and the weight average molecular weight is 10,000 to 100,000; and The coating described herein has a solvent resistance of greater than 80 MEK bi-friction as measured by ASTM D7835 and a wedge bending resistance of 70-100% (% qualified) as measured by ASTM D3281.

2. The coating composition according to claim 1, wherein the amount of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (i) is 45 mol%-55 mol%, 2-methyl-1,3-propanediol (ii) is 8 mol%-15 mol%, cyclohexanediol (iii) is 30 mol%-40 mol%, trimethylolpropane (iv) is 2 mol%-4 mol%, terephthalic acid (v) is 50 mol%-80 mol%, isophthalic acid (vi) is 16 mol%-46 mol%, and acyclic aliphatic diacid (vii) is 4 mol%-8 mol.

3. The coating composition according to claim 1, wherein the amount of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (i) is 28 mol%-60 mol%, 2-methyl-1,3-propanediol (ii) is 5 mol%-45 mol%, cyclohexanediol (iii) is 10 mol%-40 mol%, trimethylolpropane (iv) is 1 mol%-4 mol%, terephthalic acid (v) is 60 mol%-100 mol%, isophthalic acid (vi) is 0 mol%-40 mol%, and acyclic aliphatic diacid (vii) is 0 mol%-15 mol.

4. The coating composition according to claim 1, wherein the polyester polyol (a) has a hydroxyl value of 12-30 mg KOH / g and wherein the Tg of the polyester polyol (a) is 70 to 95°C.

5. The coating composition according to claim 1, wherein the crosslinking agent (b) is a methyl phenolic resin, or an isocyanate, or a mixture thereof.

6. The coating composition according to claim 1, wherein the crosslinking agent (b) is a mixture of methyl phenolic resin and isocyanate, and wherein, based on the total weight of the crosslinking agent, the amount of methyl phenolic resin is 70wt%-90wt% and the amount of isocyanate is 10wt%-30wt%.

7. The coating composition according to claim 1, wherein, based on the total weight of (a) and (b), the amount of the polyester polyol (a) is 50wt%-90wt% and the amount of the crosslinking agent (b) is 10wt%-50wt%.

8. The coating composition according to claim 1, wherein: a. Based on the total weight of (a), (b), and (c), the polyester polyol is present in an amount of 70 wt%-80 wt%, which is a reaction product of the monomer, the monomer comprising: i. 28 mol%–60 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol based on the total moles of i–iv. ii. Based on the total moles of i-iv, 5 mol%-45 mol% of 2-methyl-1,3-propanediol, iii. Based on the total moles of i-iv, 10 mol%-45 mol% of cyclohexanediethanol, iv. Based on the total number of moles in i-iv, 1 mol%-4.5 mol% of trimethylolpropane, v. Based on the total number of moles of v-vii, 45 mol%-100 mol% of terephthalic acid. vi. Based on the total number of moles of v-vii, 0 mol%-55 mol% of isophthalic acid, and vii. Based on the total number of moles in v-vii, the amount of acyclic aliphatic diacids ranging from 0 mol% to 15 mol%. b. Based on the total weight of (a), (b), and (c), 12wt%–27wt% of methyl phenolic resin, and c. Based on the total weight of (a), (b), and (c), 3 wt%–8 wt% of isophorone diisocyanate, The polyester polyol has a glass transition temperature (Tg) of 50 to 110°C, an acid value of 0 to 10 mgKOH / g, a hydroxyl value of 10 to 30 mgKOH / g, a number-average molecular weight of 5,000 to 20,000 mgKOH / g, and a weight-average molecular weight of 10,000 to 100,000; and The coating described herein has a solvent resistance of greater than 80 MEK bi-friction as measured by ASTM D7835; and a wedge bending resistance of 70-100% (% qualified) as measured by ASTM D3281.

9. The coating composition according to claim 1, wherein: a. Based on the total weight of (a) and (b), the polyester polyol is present in an amount of 80wt%-90wt% as a reaction product of the monomer, the monomer comprising: i. 28 mol%–60 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol based on the total moles of i–iv. ii. Based on the total moles of i-iv, 5 mol%-45 mol% of 2-methyl-1,3-propanediol, iii. Based on the total moles of i-iv, 10 mol%-45 mol% of cyclohexanediethanol, iv. Based on the total number of moles in i-iv, 1 mol%-4.5 mol% of trimethylolpropane, v. Based on the total number of moles of v-vii, 45 mol%-100 mol% of terephthalic acid. vi. Based on the total number of moles of v-vii, 0 mol%-55 mol% of isophthalic acid, and vii. Based on the total molar number of v-vii, an amount of 0 mol%-15 mol% of an acyclic aliphatic diacid, and b. The crosslinking agent (b) is based on the total weight of (a) and (b), an amount of 10 wt%-20 wt% of benzoguanamine formaldehyde resin, and The coating composition further comprises titanium dioxide pigment, and The polyester polyol wherein the glass transition temperature (Tg) is 50 to 110°C, the acid value is 0 to 10 mgKOH / g, the hydroxyl value is 10 to 30 mgKOH / g, the number average molecular weight is 5,000 to 20,000 mgKOH / g, and the weight average molecular weight is 10,000 to 100,000; and The coating described herein has a solvent resistance of greater than 80 MEK bi-friction as measured by ASTM D7835; and a wedge bending resistance of 70-100% (% qualified) as measured by ASTM D3281.

10. The coating composition according to claim 1, wherein: a. Based on the total weight of (a), (b), and (c), the polyester polyol is present in an amount of 70 wt%-85 wt%, which is a reaction product of the monomer, the monomer comprising: i. 28 mol%–60 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol based on the total moles of i–iv. ii. Based on the total moles of i-iv, 5 mol%-45 mol% of 2-methyl-1,3-propanediol, iii. Based on the total moles of i-iv, 10 mol%-45 mol% of cyclohexanediethanol, iv. Based on the total number of moles in i-iv, 1 mol%-4.5 mol% of trimethylolpropane, v. Based on the total number of moles of v-vii, 45 mol%-100 mol% of terephthalic acid. vi. Based on the total number of moles of v-vii, 0 mol%-55 mol% of isophthalic acid, and vii. Based on the total number of moles in v-vii, the amount of acyclic aliphatic diacids ranging from 0 mol% to 15 mol%. b. Based on the total weight of (a), (b), and (c), 10wt%–20wt% of benzoguanamine formaldehyde resin, and c. Based on the total weight of (a), (b), and (c), 5 wt%–12 wt% of isophorone diisocyanate, The coating composition further comprises titanium dioxide pigment; and The polyester polyol wherein the glass transition temperature (Tg) is 50 to 110°C, the acid value is 0 to 10 mgKOH / g, the hydroxyl value is 10 to 30 mgKOH / g, the number average molecular weight is 5,000 to 20,000 mgKOH / g, and the weight average molecular weight is 10,000 to 100,000; and The coating described herein has a solvent resistance of greater than 80 MEK bi-friction as measured by ASTM D7835 and a wedge bending resistance of 75-100% (qualified) as measured by ASTM D3281.

11. A coating composition comprising: a. Based on the total weight of (a) and (b), 80wt%-90wt% of a polyester polyol, which is a reaction product of a monomer, said monomer comprising: i. 28 mol%–60 mol% of 2,2,4,4-Tetramethyl-1,3-cyclobutanediol (TMCD) based on the total number of moles of i–iv. ii. 5 mol% to 45 mol% of 2-methyl-1,3-propanediol (MP diol) based on the total number of moles of i-iv. iii. Neopentyl glycol (NPG) in amounts ranging from 10 mol% to 45 mol% based on the total number of moles in i-iv. iv. Based on the total number of moles of i-iv, 1 mol%-4.5 mol% of trimethylolpropane (TMP). v. Terephthalic acid (TPA) in amounts of 80 mol%–100 mol% based on the total number of moles of v–vii. vi. Based on the total number of moles of v-vii, 0 mol%-20 mol% of isophthalic acid (IPA), and vii. Based on the total molar number of v-vii, the amount of acyclic aliphatic diacids ranging from 0 mol% to 15 mol%, and b. Based on the total weight of (a) and (b), 10wt%-20wt% of benzoguanamine formaldehyde resin, The coating composition further comprises titanium dioxide pigment, and the polyester polyol has a glass transition temperature (Tg) of 50 to 110°C, an acid value of 0 to 10 mg KOH / g, a hydroxyl value of 10 to 30 mg KOH / g, a number average molecular weight of 5,000 to 20,000 mg KOH / g, and a weight average molecular weight of 10,000 to 100,000; and the coating has a solvent resistance of greater than 80 MEK bi-friction as measured by ASTM D7835 and a wedge bending resistance of 65-100% (qualified) as measured by ASTM D3281.

12. A coating composition comprising: a. Based on the total weight of (a), (b), and (c), 70 wt%–85 wt% of a polyester polyol, which is a reaction product of a monomer, said monomer comprising: i. 28 mol%–60 mol% of 2,2,4,4-Tetramethyl-1,3-cyclobutanediol (TMCD) based on the total number of moles of i–iv. ii. 5 mol% to 45 mol% of 2-methyl-1,3-propanediol (MP diol) based on the total number of moles of i-iv. iii. Neopentyl glycol (NPG) in amounts ranging from 10 mol% to 45 mol% based on the total number of moles in i-iv. iv. Based on the total number of moles of i-iv, 1 mol%-4.5 mol% of trimethylolpropane (TMP). v. Terephthalic acid (TPA) in amounts of 80 mol%–100 mol% based on the total number of moles of v–vii. vi. Based on the total number of moles of v-vii, 0 mol%-20 mol% of isophthalic acid (IPA), and vii. Based on the total number of moles in v-vii, the amount of acyclic aliphatic diacids ranging from 0 mol% to 15 mol%. b. Based on the total weight of (a), (b), and (c), 10wt%–20wt% of benzoguanamine formaldehyde resin, and c. Based on the total weight of (a), (b) and (c), 5 wt%–12 wt% of isophorone diisocyanate (IPDI). The coating composition further comprises titanium dioxide pigment, and the polyester polyol has a glass transition temperature (Tg) of 50 to 110°C, an acid value of 0 to 10 mg KOH / g, a hydroxyl value of 10 to 30 mg KOH / g, a number average molecular weight of 5,000 to 20,000 mg KOH / g, and a weight average molecular weight of 10,000 to 100,000; and the coating has a solvent resistance of greater than 80 MEK bi-friction as measured by ASTM D7835 and a wedge bending resistance of 75-100% (qualified) as measured by ASTM D3281.

13. A coating composition comprising: a. Based on the total weight of (a), (b), and (c), 70 wt%–80 wt% of a polyester polyol, which is a reaction product of a monomer, said monomer comprising: i. 28 mol%–60 mol% of 2,2,4,4-Tetramethyl-1,3-cyclobutanediol (TMCD) based on the total number of moles of i–iv. ii. 5 mol% to 45 mol% of 2-methyl-1,3-propanediol (MP diol) based on the total number of moles of i-iv. iii. Neopentyl glycol (NPG) in amounts ranging from 10 mol% to 45 mol% based on the total number of moles in i-iv. iv. Based on the total number of moles of i-iv, 1 mol%-4.5 mol% of trimethylolpropane (TMP). v. Terephthalic acid (TPA) in amounts of 80 mol%–100 mol% based on the total number of moles of v–vii. vi. Based on the total number of moles of v-vii, 0 mol%-20 mol% of isophthalic acid (IPA), and vii. Based on the total number of moles in v-vii, the amount of acyclic aliphatic diacids ranging from 0 mol% to 15 mol%. b. Based on the total weight of (a), (b), and (c), 12wt%–27wt% of methyl phenolic resin, and c. Based on the total weight of (a), (b) and (c), 3 wt%–8 wt% of isophorone diisocyanate (IPDI). The polyester polyol wherein the glass transition temperature (Tg) is 50 to 110°C, the acid value is 0 to 10 mgKOH / g, the hydroxyl value is 10 to 30 mgKOH / g, the number average molecular weight is 5,000 to 20,000 mgKOH / g, and the weight average molecular weight is 10,000 to 100,000; and the coating wherein the coating has a solvent resistance greater than 80 MEK bi-friction as measured by ASTM D7835 and a wedge bending resistance of 70-100% (% qualified) as measured by ASTM D3281.

Citation Information

Patent Citations

  • Compositions for metal packaging coatings

    US20180223126A1

  • Curable polyester and thermosetting composition containing resole phenolic resin

    CN111500024A